Flame-retardant and smoke-suppressing nano-cellulose-based reinforced modified material and preparation method thereof
By combining the load-modified phosphorylated nanocellulose with modified mica nanosheets, and using CDI-amino graft modification method and dopamine modification treatment, nanosilicon dioxide was synthesized in combination with ethyl orthosilicate hydrolysis, which solved the agglomeration and compatibility problems of nanocellulose in polymer materials, and significantly improved the mechanics, flame retardant and smoke suppression properties of the material.
Patent Information
- Application Number
- CN202411692418.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-14
AI Technical Summary
When nanocellulose is used as a filler in polymer materials, it causes agglomeration, poor compatibility and poor thermal stability due to the abundant surface hydroxyl groups, which affects the mechanical properties of the composite material. At the same time, nanocellulose lacks flame retardant and smoke suppressing properties.
By combining the load-modified phosphorylated nanocellulose with modified mica nanosheets, a flame-retardant and smoke-retardant nanocellulose-based reinforced modified material was prepared. The material improves the hydrophobicity of phosphorylated nanocellulose by CDI-amino graft modification method, and enhances its dispersion stability by dopamine modification treatment. At the same time, nanosilicon dioxide is synthesized in situ by hydrolysis of ethyl orthosilicate, improving the flame retardant and smoke suppression properties of the composite material.
The mechanical properties, flame retardant and smoke suppressing properties of nanocellulose-based reinforced modified materials are significantly improved, and the agglomeration and compatibility problems of nanocellulose in polymer materials are solved, and the materials are given good flame retardant and smoke suppressing properties.
Smart Images

Figure CN119613576A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of enhanced modified materials, and relates to a flame retardant and smoke suppressing nano-cellulose-based enhanced modified material and a preparation method thereof. Background Art
[0002] Cellulose is a polymer compound composed of many D-glucose groups connected by β-1,4 glycosidic bonds. When cellulose is hydrolyzed under certain conditions and the degree of polymerization decreases to a state of equilibrium, the resulting product is called microcrystalline cellulose, with a particle size of 20 to 80 μm. In addition, nanocellulose with a lateral size of about 1 to 100 nm can be further obtained through hydrolysis, high-pressure shearing, microbial methods, dissolution methods, etc. Nanocellulose has excellent performance in high-performance reinforced composite materials, medical materials, optical materials and other fields due to its high aspect ratio, large specific surface area, high mechanical strength and good biocompatibility.
[0003] When nanocellulose is used as a filler in polymer materials to prepare composite materials, it is easy to agglomerate when mixed with matrix materials because of its rich hydroxyl groups on its surface and strong polarity, resulting in uneven dispersion, poor compatibility, poor thermal stability and other problems in the matrix, thereby affecting the mechanical properties of the composite materials. Therefore, how to improve the compatibility of nanocellulose with the matrix material and give the composite material certain flame retardant properties is a technical problem to be solved by the present invention. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a flame retardant and smoke suppressant nanocellulose-based reinforced modified material and a preparation method thereof. The present invention compounded loaded modified phosphorylated nanocellulose and modified mica nanosheets to prepare a flame retardant and smoke suppressant nanocellulose-based reinforced modified material. The reinforced modified material can be used as a performance enhancer for polymers such as coatings, rubbers, plastics, foods, and medical materials to improve the product structure and enhance the physical and chemical properties of the product, such as mechanical properties, flame retardant properties, and smoke suppression properties.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material, the preparation method comprising:
[0007] (I) mixing, stirring and heating the phosphorylated nanocellulose and N,N'-carbonyldiimidazole solution to react, and obtaining an intermediate product solution after the reaction is completed; adding an octadecylamine solution to the intermediate product solution, mixing, stirring and heating to react, filtering, washing and drying after the reaction is completed to obtain modified phosphorylated nanocellulose; dispersing the modified phosphorylated nanocellulose in a dopamine solution, mixing, stirring and heating to react, and centrifuging, washing and freeze-drying after the reaction is completed to obtain a composite modified phosphorylated nanocellulose;
[0008] (II) mixing anhydrous ethanol, an ammonia solution and deionized water to obtain a composite solvent, adding the composite modified phosphorylated nanocellulose and hexadecyltrimethylammonium bromide obtained in step (II) to the composite solvent, mixing, stirring and heating to obtain a mixed solution; under stirring and heating conditions, dripping tetraethyl orthosilicate into the mixed solution, and continuing to stir and heat for a period of time to react after all the tetraethyl orthosilicate has been dripped, filtering, washing and freeze-drying after the reaction is completed to obtain the loaded modified phosphorylated nanocellulose;
[0009] (III) subjecting sericite to high temperature calcination to obtain activated sericite; subjecting the activated sericite to acidification with a nitric acid solution to obtain acidified sericite; subjecting the acidified sericite to lithiation with lithium nitrate to obtain lithiated sericite; subjecting the lithiated sericite to intercalation modification with hexadecyltrimethylammonium bromide to obtain intercalated sericite; subjecting the intercalated sericite to ultrasonic exfoliation to obtain mica nanosheets; subjecting the mica nanosheets to surface hydrophobic modification with a silane coupling agent to obtain modified mica nanosheets;
[0010] (IV) Mixing the loaded modified phosphorylated nanocellulose obtained in step (II), the modified mica nanosheets obtained in step (III), a nonionic surfactant and deionized water to obtain a composite suspension, ultrasonically dispersing the composite suspension to obtain a composite dispersion, and spray-drying the composite dispersion to obtain the nanocellulose-based reinforced modified material.
[0011] The present invention compounds the loaded modified phosphorylated nanocellulose and the modified mica nanosheets to prepare a flame retardant and smoke suppressing nanocellulose-based reinforced modified material, which can be used as a performance enhancer for polymers such as coatings, rubbers, plastics, foods, and pharmaceutical materials to improve the product structure and improve the physical and chemical properties of the product, such as mechanical properties, flame retardant properties, and smoke suppression properties. When used, the reinforced modified material provided by the present invention can be added to the base material in a certain proportion, mixed evenly, and then produced according to conventional processes. For example, in the field of coatings, the reinforced modified material provided by the present invention can be added to the coating emulsion in a certain proportion, mixed evenly, and then coated. After drying and forming the film, a paint film coating with excellent mechanical properties, flame retardant properties, and smoke suppression properties can be obtained; in the field of plastics, the reinforced modified material provided by the present invention can be melt-blended and extruded with a polymer material in a certain proportion to obtain a plastic masterbatch with excellent mechanical properties, flame retardant properties, and smoke suppression properties.
[0012] In the present invention, there is a synergistic effect between the loaded modified phosphorylated nanocellulose and the modified mica nanosheets, which is specifically embodied in:
[0013] On the one hand, the loaded modified phosphorylated nanocellulose is a fibrous filamentous structure with a large specific surface area and a high aspect ratio. It itself has high mechanical strength. After adding it to a matrix material (such as coatings, plastics, rubber, etc.), it can form a three-dimensional network structure skeleton in the polymer matrix. When the modified mica nanosheets are evenly loaded on the three-dimensional network structure skeleton, the loaded modified phosphorylated nanocellulose can become a "physical bridge" between the modified mica nanosheets. When subjected to external forces, it can achieve smooth transfer of load stress and avoid stress concentration leading to fracture of the composite material. In addition, since the modified mica nanosheets are modified with silane coupling agents, their surfaces contain some silicon hydroxyl groups, which can combine with the large number of free hydroxyl groups on the surface of the loaded modified phosphorylated nanocellulose to produce strong hydrogen bonding. There is also hydrogen bonding between the loaded modified phosphorylated nanocellulose and the matrix material. Therefore, the loaded modified phosphorylated nanocellulose can also serve as a "chemical bridge" between the matrix material and the modified mica nanosheets. Through the dual effects of "physical bridge" and "chemical bridge", the dispersion uniformity of the modified mica nanosheets in the polymer matrix is greatly improved, thereby significantly improving the mechanical properties of the composite material.
[0014] On the other hand, the present invention synthesizes nano-silicon dioxide in situ on the surface of composite modified phosphorylated nano-cellulose by hydrolysis of ethyl orthosilicate to obtain loaded modified phosphorylated nano-cellulose. The addition of nano-silicon dioxide can significantly improve the combustion behavior of the composite material, so that the carbon layer formed after the combustion of the composite material becomes continuous and dense, and the flame retardant performance of the composite material is effectively improved; at the same time, the nano-silicon dioxide and the modified mica nano-sheets can play a synergistic role, which significantly improves the smoke suppression performance of the composite material. This is because the modified mica nano-sheets and the nano-silicon dioxide are jointly wrapped on the carbon layer, and the special layer structure of the modified mica nano-sheets can cover the surface of the composite material to prevent it from contacting with oxygen in the air, and the nano-silicon dioxide can form a mesh structure protective layer to increase the density of the carbon layer surface. The synergistic effect of the modified mica nano-sheets and the nano-silicon dioxide can significantly increase the density and thickness of the carbon layer. At the same time, a large number of silica microspheres attached to the surface of the carbon layer can effectively prevent heat release and smoke release, thereby greatly improving the flame retardant and smoke suppression properties of the composite material.
[0015] Since phosphorylated nanocellulose molecules contain a large number of hydroxyl groups and have strong intermolecular hydrogen bonding, they are very prone to agglomeration. In particular, hydrogen bonding during the drying process will cause irreversible fiber keratinization, which causes serious agglomeration of phosphorylated nanocellulose after drying and makes it difficult to redisperse it by physical methods. In order to improve the dispersion uniformity and stability of phosphorylated nanocellulose in polymer matrix materials, the present invention uses N, N′-carbonyldiimidazole (CDI) and octadecylamine to hydrophobically modify phosphorylated nanocellulose.
[0016] N, N'-carbonyldiimidazole (CDI) is a derivative of imidazole, and has a closed large P bond in its imidazole structure, and a pair of lone electrons in the unbonded sp2 orbital of one of the nitrogen atoms. These characteristics determine that CDI has strong chemical reactivity and can react with functional groups such as amino, carboxyl and hydroxyl groups. The present invention adopts a CDI-amino grafting modification method to hydrophobically modify phosphorylated nanocellulose to obtain modified phosphorylated nanocellulose, and one of the imidazole structures on the CDI molecular chain reacts with the hydroxyl group on the phosphorylated nanocellulose molecular chain to form an ester imidazole structure on the phosphorylated nanocellulose molecular chain, and then another imidazole structure on the CDI molecular chain reacts with the amino group on the octadecylamine molecular chain to form a carbamate bond between the octadecylamine molecular chain and the phosphorylated nanocellulose molecular chain, so that the octadecylamine molecular chain is firmly grafted onto the phosphorylated nanocellulose molecular chain.
[0017] The CDI-amino modification method provided by the present invention can significantly improve the hydrophobicity of phosphorylated nanocellulose, thereby greatly improving the uniformity of the dispersion of phosphorylated nanocellulose in the matrix material, and at the same time, the mechanical reinforcement of phosphorylated nanocellulose can be further enhanced. This is because octadecylamine is a low surface energy substance containing long-chain alkyl and active amino groups. The amino group in octadecylamine and the imidazole structure on the CDI molecular chain can graft the hydrophobic long chain of octadecylamine on the surface of phosphorylated nanocellulose to give it hydrophobicity. The low surface energy octadecylamine molecular chain can also significantly improve the dispersibility of phosphorylated nanocellulose, thereby reducing the agglomeration of phosphorylated nanocellulose; at the same time, the brush-like structure formed by the octadecylamine molecular chain on the surface of phosphorylated nanocellulose can also effectively avoid the flocculation of phosphorylated nanocellulose, and promote the formation of the phosphorylated nanocellulose reinforcement network, thanks to the uniform dispersion of phosphorylated nanocellulose in the matrix material and the formation of the reinforcement network, so that the mechanical properties of the composite material are significantly enhanced. In addition, thanks to the excellent chemical stability of the carbamate bond, it has good tolerance to acidic and alkaline environments, and the hydrophobic durability of the composite material finally formed is also significantly improved.
[0018] In order to further improve the dispersion stability of modified phosphorylated nanocellulose in the matrix material, the present invention adds dopamine modification treatment on the basis of CDI-amino grafting modification method. Dopamine can undergo self-polymerization under aerobic weak alkaline conditions to generate a viscous substance polydopamine. After dopamine is oxidized to dopamine quinone, it is easy to undergo Michael addition reaction or Schiff base reaction with organic molecules containing amino, thiol or imino groups. Based on this, the present invention first grafts octadecylamine long chains on the surface of phosphorylated nanocellulose through CDI-amino grafting modification method to obtain modified phosphorylated nanocellulose, and then uses dopamine oxidation self-polymerization to modify the modified phosphorylated nanocellulose to obtain composite modified phosphorylated nanocellulose.
[0019] The purpose of dopamine modification treatment is that, on the one hand, the hydrophobic long chain of octadecylamine can significantly reduce the surface energy of modified phosphorylated nanocellulose, and the hydrophobic long chain of octadecylamine can be reinforced by the adhesion of polydopamine, which can ensure that the hydrophobic long chain of octadecylamine is wear-resistant and not easy to fall off, maintain the long-term hydrophobicity of the composite material, and make the composite material still have good hydrophobicity after hundreds of frictions; on the other hand, polydopamine can react with octadecylamine to produce Schiff base, and adsorb the free octadecylamine in the solution on the surface of modified phosphorylated nanocellulose through its own adhesion, so as to construct a rough structure on the surface of modified phosphorylated nanocellulose. Through the synergistic effect between dopamine and octadecylamine, the surface energy of modified phosphorylated nanocellulose can be further reduced and a large number of rough structures can be constructed, thereby significantly improving the dispersion stability of modified phosphorylated nanocellulose in the matrix material.
[0020] In order to further improve the flame retardant properties, smoke suppression properties and mechanical properties of the composite material, the present invention synthesizes nano-silicon dioxide in situ on the surface of composite modified phosphorylated nanocellulose by hydrolyzing tetraethyl orthosilicate, and the introduction of nano-silicon dioxide can further improve the flame retardant properties, smoke suppression properties and mechanical properties of the composite material. This is because, on the one hand, the addition of nano-silicon dioxide significantly affects the combustion behavior of the composite material, improves the barrier protection effect of the carbon layer, and the nano-silicon dioxide will migrate to the surface of the composite material during the combustion process of the composite material. The residual carbon formed by the combustion of nano-silicon dioxide is connected on the surface of the composite material to form a mesh structure protective layer, thereby improving the strength of the carbon layer, making the carbon layer formed after combustion continuous and dense, playing a certain heat insulation protection role, and can effectively prevent the volatilization and dripping of degradation products, thereby significantly improving the flame retardant properties and smoke suppression properties of the composite material. On the other hand, the molecular chain of the composite modified phosphorylated nanocellulose contains a large number of hydroxyl groups, has a large number of reactive sites, and can be cross-linked with the hydroxyl groups generated after the hydrolysis of tetraethyl orthosilicate to form an interpenetrating three-dimensional network structure, thereby significantly improving the mechanical properties of the composite material.
[0021] Mica nanosheets are a two-dimensional sheet filler. After adding an appropriate amount of mica nanosheets to the matrix material, the barrier property of the composite material surface can be significantly improved to provide good flame retardant and smoke suppression performance. The present invention uses sericite as a raw material, and obtains mica nanosheets through high-temperature activation, acidification, lithiation, intercalation modification and ultrasonic stripping. However, due to the hydrophilicity of mica nanosheets, the dispersibility in the matrix material is poor and they are easy to agglomerate in the matrix material, which hinders the advantages of mica nanosheets in the composite material. Therefore, the present invention hydrophobically modifies the mica nanosheets to improve their uniformity of dispersion in the matrix material.
[0022] Sericite is a silicate mineral with a layered structure. During the high-temperature activation process, the OH - Desorption and conversion into interlayer water. During the calcination process, the temperature difference between the inside and outside of the sericite flakes is large, resulting in a large temperature gradient between the middle and edge areas of the flakes. The interlayer water discharge rate in the edge area is faster, and the water is enriched around the sericite, sealing the internal space between the layers of the sericite. Water loss and sealing occurs in the edge area of the sericite flakes, making it difficult to discharge the water in the middle area of the layer, resulting in a higher vapor pressure in the middle area of the layer, forcing the sericite flakes to expand, which is beneficial to the subsequent organic intercalation treatment of hexadecyltrimethylammonium bromide.
[0023] The physical and chemical structure of sericite is a compound silicon-oxygen layer consisting of two layers of silicon-oxygen tetrahedrons [(Si,Al)-O4] and a middle layer of aluminum-oxygen octahedrons [AlO2(OH)4]. The interlayer cations are mainly potassium ions and magnesium ions. Since potassium ions and magnesium ions have larger ion radius, higher charge density, and larger ion hydration number, there are more water molecules around potassium ions and magnesium ions and they are more firmly bound, which makes potassium ions and magnesium ions lose their ion exchange capacity, which is not conducive to organic intercalation modification. At the same time, potassium ions are just embedded in two hexagonal meshes facing each other on adjacent crystal planes, forming 12 times coordination, and the interlayer charge is close to neutrality. The potassium ions are very tightly bound to the crystal planes, and the interlayer spacing is relatively fixed, which makes the exchangeable ion concentration of sericite low and the interlayer charge very stable. Even if the sheets expand after high-temperature activation, due to the weak ion exchange capacity, it is difficult for hexadecyltrimethylammonium bromide to enter the interlayers of sericite through ion exchange for intercalation modification. To this end, the present invention performs acidification and lithiation treatment on the sericite after high-temperature activation, thereby increasing the interlamellar spacing of the sericite through high-temperature activation and increasing the exchangeable ion concentration between the sericite lamellae through acidification and lithiation, thereby greatly promoting the organic intercalation modification of hexadecyltrimethylammonium bromide.
[0024] Since Al-O tetrahedron is not as stable as Si-O tetrahedron, acidification of sericite can destroy Al-O tetrahedron, dissolve Al in tetrahedron preferentially and deplete it, destroying interlayer ionization balance and enhancing interlayer activity. + It can replace most of the interlayer magnesium ions and dissolve a small amount of cations in the aluminum oxide octahedron, so that some impurities between the sericite sheets are dissolved by acid, the interlayer channels are unblocked, and the diffusion and adsorption capacity of molecules between the layers is improved. In addition, after acid treatment, a large number of fine grooves appear on the surface of the sericite sheets, which increases the surface roughness, ion adsorption area and surface electrical properties of the sericite, and improves the ion exchange capacity between the sericite sheets. After acid treatment, some interlayer ions such as aluminum ions, magnesium ions, calcium ions and potassium ions are dissolved, and the interlayer charge is destroyed. Subsequently, lithium treatment is performed to further improve the interlayer ion exchange capacity of sericite. Since the ion radius of lithium ions is relatively small, the charge density is low, the binding energy between the sheets of sericite is weak, the hydration energy is low, and the hydration ion radius is large, the cations are easier to exchange ions with the outside world, thereby increasing the exchangeable ion concentration between the sericite sheets, which is beneficial to organic intercalation modification.
[0025] Through the early high-temperature activation, acidification and lithiation treatment, the layers of sericite have exchangeable water molecules and cations. At this time, the concentration of exchangeable cations is relatively high, and the hexadecyltrimethylammonium bromide molecules can enter the layers of sericite through cation exchange to obtain intercalated sericite. When the ammonium ions in hexadecyltrimethylammonium bromide enter the sericite lamellae through ion exchange, the sericite lamellae are stretched open by the cleavage plane, and the alkyl chains then enter the lamellae. After entering the lamellae, hexadecyltrimethylammonium bromide adopts the most stable spatial form for arrangement. When the concentration of hexadecyltrimethylammonium bromide is low, the alkyl chains are arranged parallel to the lamellae surface. As the concentration of hexadecyltrimethylammonium bromide increases, the alkyl chains continue to enter the interlayers of sericite, the angle with the lamellae surface becomes larger, and the single layer is transformed into a double layer until the concentration of hexadecyltrimethylammonium bromide increases to form a double-layer structure and arrange at a large angle. Due to the spatial form and distribution of the alkyl chains between the sericite lamellae, the spacing between the sericite lamellae is forced to expand. Under the action of ultrasonic-assisted exfoliation, the overlapping lamellae of sericite are finally completely exfoliated to form mica nanosheets.
[0026] The present invention uses a silane coupling agent to hydrophobically modify mica nanosheets. The silane coupling agent is hydrolyzed under the action of deionized water to generate silanols. The generated silanols undergo a condensation reaction to form silane oligomers. The silane oligomers further react with hydroxyl groups on the surface of the mica nanosheets to generate silicon oxygen bonds after dehydration condensation, thereby being grafted on the surface of the mica nanosheets to achieve hydrophobic modification of the mica nanosheets. In addition, the mechanical reinforcement effect of the modified mica nanosheets can be improved by modification with a silane coupling agent. This is because the silane coupling agent plays a cross-linking role between the modified mica nanosheets, so that the cross-linking density of the composite material added with the enhanced modified material provided by the present invention is increased, and cracks and holes on the surface and inside of the composite material are reduced, resulting in a more compact composite material formed in the end, giving the composite material higher mechanical properties.
[0027] As a preferred technical solution of the present invention, in step (I), the phosphorylated nanocellulose is prepared by the following method:
[0028] The cellulose raw material is subjected to steam explosion to obtain raw fiber, the raw fiber, phosphate, urea and deionized water are mixed to obtain a suspension, the suspension is heated and crushed at the same time to obtain a mixed material; the mixed material is sent to a screw extruder for extrusion dehydration to obtain a wet material; the wet material is sequentially heated and dried and high-temperature cured to obtain phosphorylated cellulose; the phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed liquid, the cellulose mixed liquid is sequentially subjected to mechanical grinding and high-pressure homogenization to obtain the phosphorylated nanocellulose.
[0029] The present invention prepares phosphorylated nanocellulose through phosphorylation and nano-processing, and adding the phosphorylated nanocellulose to a polymer matrix can significantly improve the mechanical properties and flame retardant properties of the composite material. This is because, on the one hand, the phosphorylated nanocellulose has a crystalline region and a non-crystalline region along the length of the cellulose molecular chain, the crystalline region has a large density, has natural hydrophobic properties, and the three-dimensional hydrogen bond network structure formed between and within the phosphorylated nanocellulose molecules gives the composite material higher mechanical properties. On the other hand, after phosphorylation, the phosphorylated nanocellulose can be promoted to undergo decarboxylation and dehydration reactions, and the carbonization process of the phosphorylated nanocellulose can be accelerated, so that the peak heat release rate time is advanced, and the residual rate of the phosphorylated nanocellulose is higher. After combustion, more coke layers are attached to the surface of the composite material, which can form a physical barrier, play a role in heat insulation protection, and inhibit the combustion behavior; in addition, the non-combustible gas (such as H2O, CO2) released by the phosphorylated nanocellulose during the combustion process can also effectively dilute the combustible gas, thereby reducing the temperature of the combustion zone, and further reducing the possibility of combustion, and significantly improving the flame retardant properties of the composite material.
[0030] In the process of preparing phosphorylated nanocellulose, the present invention first performs steam explosion on the cellulose raw material, and steam explosion is to treat the cellulose raw material with hot steam under a certain pressure, and then perform explosive decompression on the cellulose raw material. This pretreatment combines the chemical action of the self-hydrolysis of acetyl groups in hemicellulose with mechanical action. In the hot steam treatment process, the cellulose raw material is under high temperature and high pressure conditions, and water vapor will penetrate into the interior of the fiber molecules, and part of the water vapor will form hydrogen bonds with the hydroxyl groups in the fiber molecules, destroying the hydrogen bonding between the original hydroxyl groups in the interior of the cellulose molecules. After the pressure is suddenly released, the water molecules will burst instantly under the negative pressure, and this phenomenon is also called the cavitation effect, which causes the cellulose to produce mechanical fractures, and the hydrogen bonds formed by water vapor and the interior of the cellulose will disappear, which is conducive to the cavitation effect to play a role, destroying the force between the molecules inside the fiber, and the fiber is separated due to the mechanical action. In addition, high temperature promotes the generation of carboxyl groups by acetyl groups, and hemicellulose begins to self-hydrolyze. At the same time, water can also play the role of acid, and as part of the hemicellulose is dissolved or degraded, lignin is redistributed and partially removed. The separation of cellulose and the removal of hemicellulose fully expose the surface of cellulose, which promotes the interaction between phosphate and urea and cellulose. The steam explosion treatment can significantly improve the thermal stability and flame retardant properties of the fiber.
[0031] After the steam explosion treatment, the raw fiber obtained by the present invention is heated, soaked and broken up in a mixed solution of phosphate and urea, so that the raw fiber is fully swollen, and the phosphate and urea are caused to penetrate into the structure of the raw fiber and be fully adsorbed. On the one hand, the adsorption modification of phosphate is conducive to obtaining phosphorylated nanocellulose with high charge and flame retardant performance, and the phosphorylated nanocellulose with high charge is more conducive to its uniform dispersion in the matrix material. On the other hand, urea as a nitrogen flame retardant is a synergist of phosphate flame retardant, because the nitrogen-containing gas can promote the expansion of the residue and can be used as an inert gas to dilute the fuel, so that the charred layer is rich in carbon, and the generated gas contains fewer carbon atoms, which ultimately leads to lower combustion heat.
[0032] The present invention adopts mechanical screw extrusion dehydration to remove part of the flowing liquid in the mixture, reduce the water content of the mixture, and further reduce the energy consumption of the subsequent heating drying and high-temperature curing process. During the extrusion dehydration process, the mixture moves forward under the action of gravity and the friction between the mixture and the screw, which produces an extrusion effect on the mixture. The water in the mixture is discharged through the drainage hole of the screw extruder. As the mixture is continuously transmitted along the screw, the water in the mixture is continuously extruded and discharged; at the same time, a shearing effect is generated between the mixture and the screw. The mixture is squeezed and sheared by the screw, causing the cellulose in the mixture to be twisted, cut, separated, and swollen. The fiber cell wall in the mixture is further destroyed to form a loose structure area, which is more conducive to the penetration and infiltration of phosphate and urea.
[0033] In an alternative embodiment, the cellulosic raw material includes bleached hardwood pulp or bleached softwood pulp.
[0034] In an optional example, the steam pressure of the steam explosion is 1-2 MPa, for example, 1.0 MPa, 1.1 MPa, 1.2 MPa, 1.3 MPa, 1.4 MPa, 1.5 MPa, 1.6 MPa, 1.7 MPa, 1.8 MPa, 1.9 MPa or 2.0 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] In an optional embodiment, the steam temperature of the steam explosion is 180-200°C, for example, it can be 180°C, 182°C, 184°C, 186°C, 188°C, 190°C, 192°C, 194°C, 196°C, 198°C or 200°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In an optional example, the processing time of the steam explosion is 5 to 10 min, for example, it can be 5.0 min, 5.5 min, 6.0 min, 6.5 min, 7.0 min, 7.5 min, 8.0 min, 8.5 min, 9.0 min, 9.5 min or 10.0 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In an optional example, the mass fraction of the raw fiber in the suspension is 5~10wt%, for example, it can be 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] In an optional example, the concentration of phosphate in the suspension is 0.2~0.3kg / L, for example, it can be 0.2kg / L, 0.21kg / L, 0.22kg / L, 0.23kg / L, 0.24kg / L, 0.25kg / L, 0.26kg / L, 0.27kg / L, 0.28kg / L, 0.29kg / L or 0.3kg / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] In an optional example, the phosphate includes any one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, dilithium hydrogen phosphate or lithium dihydrogen phosphate, or a combination of at least two thereof.
[0040] In an optional example, the concentration of urea in the suspension is 0.4-0.5 kg / L, for example, it can be 0.4 kg / L, 0.41 kg / L, 0.42 kg / L, 0.43 kg / L, 0.44 kg / L, 0.45 kg / L, 0.46 kg / L, 0.47 kg / L, 0.48 kg / L, 0.49 kg / L or 0.5 kg / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] In an optional embodiment, the heating temperature of the suspension is 60-80°C, for example, it can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0042] In an optional embodiment, the heating time of the suspension is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In an optional embodiment, the screw speed of the screw extruder is 10~20rpm, for example, it can be 10rpm, 11rpm, 12rpm, 13rpm, 14rpm, 15rpm, 16rpm, 17rpm, 18rpm, 19rpm or 20rpm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] In an optional example, the moisture content of the wet material is 60-70wt%, for example, it can be 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt%, 66wt%, 67wt%, 68wt%, 69wt% or 70wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In an optional embodiment, the heating and drying temperature is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In an optional embodiment, the heating and drying time is 40 to 50 minutes, for example, it can be 40 minutes, 41 minutes, 42 minutes, 43 minutes, 44 minutes, 45 minutes, 46 minutes, 47 minutes, 48 minutes, 49 minutes or 50 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In an optional embodiment, the high temperature curing temperature is 150-160°C, for example, it can be 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In an optional example, the high temperature curing time is 20 to 30 minutes, for example, it can be 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, 25 minutes, 26 minutes, 27 minutes, 28 minutes, 29 minutes or 30 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] In an optional example, the mass fraction of the phosphorylated cellulose in the cellulose mixture is 0.5-1.5wt%, for example, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In an optional embodiment, the mechanical grinding is performed in a colloid mill.
[0051] In an optional embodiment, the rotation speed of the colloid mill is 2500~3000r / min, for example, it can be 2500r / min, 2550r / min, 2600r / min, 2650r / min, 2700r / min, 2750r / min, 2800r / min, 2850r / min, 2900r / min, 2950r / min or 3000r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] In an optional embodiment, the mechanical grinding time is 2 to 3 hours, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In an optional example, the pressure of the high-pressure homogenization is 70~100MPa, for example, it can be 70MPa, 75MPa, 80MPa, 85MPa, 90MPa, 95MPa or 100MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In an optional example, the high-pressure homogenization time is 60 to 90 minutes, for example, it can be 60 minutes, 65 minutes, 70 minutes, 75 minutes, 80 minutes, 85 minutes or 90 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] As a preferred technical solution of the present invention, in step (I), the N,N'-carbonyldiimidazole solution consists of N,N'-carbonyldiimidazole and dichloromethane.
[0056] In an optional example, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.2~0.3 mol / L, for example, it can be 0.2mol / L, 0.21mol / L, 0.22mol / L, 0.23mol / L, 0.24mol / L, 0.25mol / L, 0.26mol / L, 0.27mol / L, 0.28mol / L, 0.29mol / L or 0.3mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In an optional example, the mass ratio of the phosphorylated nanocellulose to the N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:(1~1.2), for example, it can be 1:1.0, 1:1.02, 1:1.04, 1:1.06, 1:1.08, 1:1.1, 1:1.12, 1:1.14, 1:1.16, 1:1.18 or 1:1.2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] In an optional example, the mixing and stirring time of the phosphorylated nanocellulose and the N,N'-carbonyldiimidazole solution is 10 to 12 hours, for example, it can be 10 hours, 10.2 hours, 10.4 hours, 10.6 hours, 10.8 hours, 11 hours, 11.2 hours, 11.4 hours, 11.6 hours, 11.8 hours or 12 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] In an optional example, the temperature for mixing and stirring the phosphorylated nanocellulose and the N,N'-carbonyldiimidazole solution is 40-50°C, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] In an optional example, the octadecylamine solution consists of octadecylamine and dichloromethane.
[0061] In an optional example, the concentration of octadecylamine in the octadecylamine solution is 0.2-0.3 mol / L, for example, it can be 0.2 mol / L, 0.21 mol / L, 0.22 mol / L, 0.23 mol / L, 0.24 mol / L, 0.25 mol / L, 0.26 mol / L, 0.27 mol / L, 0.28 mol / L, 0.29 mol / L or 0.3 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] In an optional example, the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:(1.1~1.2), for example, it can be 1:1.1, 1:1.11, 1:1.12, 1:1.13, 1:1.14, 1:1.15, 1:1.16, 1:1.17, 1:1.18, 1:1.19 or 1:1.2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] The present invention particularly defines that the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:(1.1-1.2). With the increase in the amount of octadecylamine, the hydrophobicity of the modified phosphorylated nanocellulose finally obtained first increases and then tends to be stable. This is because, with the increase in octadecylamine, the hydrophobic long chains of octadecylamine grafted onto the phosphorylated nanocellulose molecular chain increase, and the hydrophobicity increases accordingly. When the amount of octadecylamine used exceeds the upper limit of the range defined by the present invention, since the number of hydroxyl functional groups on the phosphorylated nanocellulose molecular chain is certain, the N,N'-carbonyldiimidazole that reacts with the hydroxyl functional groups is certain, so when octadecylamine is added in excess, the reaction of octadecylamine and N,N'-carbonyldiimidazole reaches saturation, and there is no imidazole structure that continues to react with octadecylamine. Continuing to increase the amount of octadecylamine will not lead to an increase in the grafting rate of octadecylamine, and the hydrophobicity of the modified phosphorylated nanocellulose finally obtained will not continue to increase.
[0064] In an optional example, the mixing and stirring time of the intermediate product solution and the octadecylamine solution is 10 to 12 hours, for example, it can be 10 hours, 10.2 hours, 10.4 hours, 10.6 hours, 10.8 hours, 11 hours, 11.2 hours, 11.4 hours, 11.6 hours, 11.8 hours or 12 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] The present invention particularly limits the mixing and stirring time of the intermediate product solution and the octadecylamine solution to 10 to 12 hours. As the reaction time is prolonged, the hydrophobicity of the modified phosphorylated nanocellulose finally obtained first increases and then tends to be stable. This is because, when the reaction time is less than 10 hours, the reaction of the imidazole structure on the N, N'-carbonyldiimidazole molecular chain with the amino group on the octadecylamine molecular chain is not complete. At this time, there are still a large number of free octadecylamine molecules in the reaction system, and the number of octadecylamine molecules grafted onto the phosphorylated nanocellulose molecular chain is relatively small. When the reaction time reaches 12 hours, the reaction of the imidazole structure on the N, N'-carbonyldiimidazole molecular chain with the amino group on the octadecylamine molecular chain is complete. At this time, the number of octadecylamine grafted onto the phosphorylated nanocellulose molecular chain reaches a maximum value, the hydrophobicity reaches a maximum, and further extension of the reaction time will not lead to an increase in the grafting rate of octadecylamine, and the hydrophobicity will not continue to increase.
[0066] In an optional example, the temperature for mixing and stirring the intermediate product solution and the octadecylamine solution is 40-50°C, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0067] The present invention particularly limits the mixing and stirring temperature of the intermediate product solution and the octadecylamine solution to 40-50° C. As the reaction temperature increases, the hydrophobicity of the modified phosphorylated nanocellulose finally obtained shows a trend of first increasing and then decreasing. This is because, when the reaction temperature is lower than 40° C., the octadecylamine has not yet completely melted, and there are still blocky octadecylamine solids in the reaction system. As the reaction temperature increases, the octadecylamine gradually melts, the reaction rate between N,N'-carbonyldiimidazole and octadecylamine gradually increases, the octadecylamine grafted onto the phosphorylated nanocellulose molecular chain gradually increases, and the hydrophobicity of the modified phosphorylated nanocellulose gradually increases; when the reaction temperature is higher than 50° C., the octadecylamine molecules grafted onto the phosphorylated nanocellulose dissolve and fall off due to the excessively high temperature, resulting in a further decrease in the hydrophobicity of the modified phosphorylated nanocellulose.
[0068] In an optional example, the dopamine solution is prepared by the following method:
[0069] Dopamine is dissolved in deionized water to obtain a mixed solution with a concentration of 1-2 g / L, and Tris-HCl buffer is added to the mixed solution to adjust the pH value of the mixed solution to 8.5 to obtain the dopamine solution, wherein the concentration of the mixed solution can be 1.0 g / L, 1.1 g / L, 1.2 g / L, 1.3 g / L, 1.4 g / L, 1.5 g / L, 1.6 g / L, 1.7 g / L, 1.8 g / L, 1.9 g / L or 2.0 g / L, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0070] Dopamine is easy to generate the adhesive substance polydopamine under weak alkaline conditions. Polydopamine can be deposited on the surface of modified phosphorylated nanocellulose through hydrogen bonds or covalent bonds. In addition, the catechol functional groups contained in dopamine can be oxidized into quinone structures and undergo Michael addition or Schiff base reactions with the amino groups in octadecylamine. Therefore, polydopamine can be used to reinforce the long hydrophobic chains of octadecylamine on the surface of modified phosphorylated nanocellulose, which can effectively prevent the octadecylamine molecular chains from falling off, so as to achieve a long-lasting hydrophobic effect.
[0071] The present invention particularly limits the concentration of dopamine in the mixed solution to 1-2 g / L. When the concentration of dopamine in the mixed solution is lower than 1 g / L, the generated polydopamine is insufficient to coat all the hydrophobic long chains of octadecylamine on the surface of the modified phosphorylated nanocellulose. When the concentration of dopamine in the mixed solution exceeds 2 g / L, desorption will occur when the concentration of dopamine in the mixed solution exceeds the equilibrium adsorption value.
[0072] In an optional example, the mass ratio of the modified phosphorylated nanocellulose to dopamine in the dopamine solution is 100:(8~10), for example, it can be 100:8.0, 100:8.2, 100:8.4, 100:8.6, 100:8.8, 100:9.0, 100:9.2, 100:9.4, 100:9.6, 100:9.8 or 100:10.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0073] In an optional embodiment, the mixing and stirring time of the modified phosphorylated nanocellulose and the dopamine solution is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0074] In an optional embodiment, the temperature for mixing and stirring the modified phosphorylated nanocellulose and the dopamine solution is 40-50°C, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0075] In an optional example, the centrifugal rotation speed is 6000~8000r / min, for example, it can be 6000r / min, 6200r / min, 6400r / min, 6600r / min, 6800r / min, 7000r / min, 7200r / min, 7400r / min, 7600r / min, 7800r / min or 8000r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0076] In an optional example, the centrifugation time is 20 to 30 min, for example, it can be 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0077] In an optional embodiment, the freeze-drying temperature is -50~-60°C, for example, it can be -50°C, -51°C, -52°C, -53°C, -54°C, -55°C, -56°C, -57°C, -58°C, -59°C or -60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0078] In an optional embodiment, the freeze-drying time is 24 to 48 hours, for example, it can be 24 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours, 46 hours or 48 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0079] As a preferred technical solution of the present invention, in step (II), the volume ratio of the anhydrous ethanol, the ammonia solution and the deionized water is 1:(0.03-0.05):(1.5-2.5), for example, it can be 1:0.03:1.5, 1:0.032:1.6, 1:0.034:1.7, 1:0.036:1.8, 1:0.038:1.9, 1:0.04:2, 1:0.042:2.1, 1:0.044:2.2, 1:0.046:2.3, 1:0.048:2.4 or 1:0.05:2.5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0080] In an optional example, the mass fraction of the ammonia solution is 25~30wt%, for example, it can be 25wt%, 25.5wt%, 26wt%, 26.5wt%, 27wt%, 27.5wt%, 28wt%, 28.5wt%, 29wt%, 29.5wt% or 30wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0081] In an optional example, the mixing ratio of the composite modified phosphorylated nanocellulose, the hexadecyltrimethylammonium bromide and the composite solvent is (0.1-0.15) g: (0.15-0.2) g: 100 mL, for example, 0.1 g: 0.15 g: 100 mL, 0.105 g: 0.16 g: 100 mL, 0.11 g: 0.165 g: 100 mL, 0.115 g: 0.17 g: 100 mL, 0.12g: 0.175g: 100mL, 0.125g: 0.8g: 100mL, 0.13g: 0.85g: 100mL, 0.135g: 0.19g: 100mL, 0.14g: 0.195g: 100mL, 0.145g: 0.2g: 100mL or 0.15g: 0.2g: 100mL, but it is not limited to the listed values, other values not listed within the numerical range are also applicable.
[0082] In an optional example, the mixing and stirring time of the composite modified phosphorylated nanocellulose, the hexadecyltrimethylammonium bromide and the composite solvent is 1 to 2 hours, for example, it can be 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2.0 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0083] In an optional example, the temperature for mixing and stirring the composite modified phosphorylated nanocellulose, the hexadecyltrimethylammonium bromide and the composite solvent is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0084] In an optional embodiment, ethyl orthosilicate is added dropwise to the mixed solution under stirring and heating conditions at 30-40°C, for example, the temperature may be 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C or 40°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0085] In an optional example, the mass ratio of the composite modified phosphorylated nanocellulose to tetraethyl orthosilicate in the mixed solution is 1:(0.1~0.2), for example, it can be 1:0.1, 1:0.11, 1:0.12, 1:0.13, 1:0.14, 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19 or 1:0.2, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0086] The addition of nano-silica can effectively improve the limiting oxygen index of the composite material. This is because, during the combustion process, nano-silica with a higher specific surface area covers the surface of the carbon layer, which improves the density of the carbon layer and effectively reduces the pores on the surface of the carbon layer. The dense carbon layer can effectively block the transfer of heat, oxygen and combustible gas to the combustible material, thereby isolating heat and achieving a better flame retardant effect, thereby reducing the heat release and smoke release of the composite material and improving the flame retardant and smoke suppression properties of the composite material.
[0087] In order to better exert the flame retardant performance of nano silicon dioxide, the present invention further defines the mass ratio of the composite modified phosphorylated nano cellulose to tetraethyl orthosilicate in the mixed solution as 1: (0.1~0.2). When the amount of tetraethyl orthosilicate is lower than the lower limit of the range defined by the present invention, the nano silicon dioxide generated by hydrolysis is too little, and it is difficult to form a continuous and dense carbon layer, thereby affecting the flame retardant performance and smoke suppression performance of the composite material. When the amount of tetraethyl orthosilicate exceeds the upper limit of the range defined by the present invention, the nano silicon dioxide generated by hydrolysis is too much. Since the surface energy of nano silicon dioxide is too large and there are hydroxyl groups on the surface, hydrogen bonds are easily formed. Excessive nano silicon dioxide will have a serious agglomeration effect in the matrix material. In the blending process of the components of the matrix material, the agglomerated nano silicon dioxide will seriously hinder the molecular chain movement of each component, so that the components in the matrix material are unevenly distributed, and the flame retardant performance decreases accordingly. In addition, due to the increase of silicon element, the rigidity of the carbon layer is too high, which easily causes the carbon layer to break and cause the flammable gas to overflow, the extinguishing time of the composite material is extended, and the flame retardant performance deteriorates.
[0088] In an optional example, after all the ethyl orthosilicate is dropped, stirring is continued for 2 to 3 hours under heating conditions of 30 to 40°C, wherein the heating temperature may be 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C or 40°C, and the stirring time may be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0089] In an optional embodiment, the freeze-drying temperature is -50~-60°C, for example, it can be -50°C, -51°C, -52°C, -53°C, -54°C, -55°C, -56°C, -57°C, -58°C, -59°C or -60°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0090] In an optional embodiment, the freeze-drying time is 24 to 48 hours, for example, it can be 24 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 36 hours, 38 hours, 40 hours, 42 hours, 44 hours, 46 hours or 48 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0091] As a preferred technical solution of the present invention, in step (III), the heating temperature of the high temperature calcination is 750-850°C, for example, it can be 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C or 850°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0092] In an optional embodiment, the holding time for high temperature calcination is 1 to 2 hours, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0093] In an optional example, the acidification process includes: dispersing the activated sericite in a nitric acid solution, mixing, stirring and heating, and then filtering, washing and drying to obtain the acidified sericite.
[0094] In an optional example, the concentration of the nitric acid solution is 8~12 mol / L, for example, it can be 8 mol / L, 8.5 mol / L, 9 mol / L, 9.5 mol / L, 10 mol / L, 10.5 mol / L, 11 mol / L, 11.5 mol / L or 12 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0095] The present invention particularly limits the concentration of the nitric acid solution to 8-12 mol / L, and the amount of aluminum ions dissolved increases with the increase of the concentration of the nitric acid solution, because the higher the concentration of hydrogen ions, the more favorable it is for adsorption on the sericite crystal surface, thereby destroying the Al-O bond and Si-O bond in the lamella lattice, and dissolving the aluminum ions in the tetrahedron and octahedron. Since the hydrogen ions first replace the cations such as potassium ions and sodium ions between the layers after entering the lamella, and then dissolve the aluminum ions and silicon ions with four-coordinate and six-coordinate coordination, therefore, in a high-concentration hydrogen ion environment, after the replacement and dissolution of part of the aluminum ions, there are still high-concentration hydrogen ions to promote the further dissolution of the aluminum ions. When the concentration of the nitric acid solution exceeds the upper limit of the range defined in the present invention, the dissolution efficiency of aluminum ions gradually decreases. This is related to the aluminum ion content in the sericite flakes and the aluminum ion concentration in the solution. As the nitric acid solution continuously dissolves aluminum ions, the concentration of aluminum ions in the surface layer of the sericite continues to decrease, while the concentration of aluminum ions in the solution near the contact surface continues to increase, prompting the replacement and aluminum ion dissolution to reach a chemical equilibrium, ultimately reducing the dissolution rate of aluminum ions.
[0096] In an optional example, the ratio of the activated sericite to the nitric acid solution is (2~4) g:100 mL, for example, it can be 2.0 g:100 mL, 2.2 g:100 mL, 2.4 g:100 mL, 2.6 g:100 mL, 2.8 g:100 mL, 3.0 g:100 mL, 3.2 g:100 mL, 3.4 g:100 mL, 3.6 g:100 mL, 3.8 g:100 mL or 4.0 g:100 mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0097] In an optional example, the mixing and stirring time of the activated sericite and the nitric acid solution is 4 to 5 hours, for example, it can be 4.0 hours, 4.1 hours, 4.2 hours, 4.3 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.7 hours, 4.8 hours, 4.9 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0098] In an optional example, the temperature for mixing the activated sericite and the nitric acid solution is 80-90°C, for example, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0099] In an optional example, the lithiation process includes:
[0100] The acidified sericite and lithium nitrate are uniformly mixed to obtain a mixed powder; the mixed powder is sent into a muffle furnace for calcination to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain the lithiated sericite.
[0101] In an optional example, the mass ratio of the acidified sericite to the lithium nitrate is 1:(8~10), for example, it can be 1:8.0, 1:8.2, 1:8.4, 1:8.6, 1:8.8, 1:9.0, 1:9.2, 1:9.4, 1:9.6, 1:9.8 or 1:10.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0102] In an optional embodiment, the calcination temperature of the mixed powder is 300-400°C, for example, it can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0103] In an optional example, the calcination time of the mixed powder is 5 to 6 hours, for example, it can be 5.0h, 5.1h, 5.2h, 5.3h, 5.4h, 5.5h, 5.6h, 5.7h, 5.8h, 5.9h or 6.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0104] The present invention specifically limits the calcination time of the mixed powder to 5 to 6 hours. When the calcination time is less than 5 hours, the lithium ions lack sufficient time to replace the interlayer cations, and the lithium modification effect is not ideal. As the reaction time increases, there is sufficient time for the ion exchange reaction, and the finally obtained lithiated sericite has a high cation exchange capacity, which provides a sufficient number of exchangeable cations for the later organic intercalation modification, so that the organic intercalation modification can be carried out smoothly. When the calcination time exceeds 6 hours, the ion exchange reaction reaches equilibrium, and the number of exchangeable cations between the sericite sheets reaches saturation. Continuing to increase the calcination time will not only not increase the cation exchange concentration between the sericite sheets, but also affect the sheet structure of the sericite, so that the barrier property of the mica nanosheets is reduced, and the flame retardant and smoke suppression properties of the composite material are affected.
[0105] As a preferred technical solution of the present invention, in step (III), the intercalation modification process includes:
[0106] The lithiated sericite is dispersed in deionized water to obtain a sericite solution, hexadecyltrimethylammonium bromide is added to the sericite solution, the mixture is stirred and heated, and then the intercalated sericite is obtained after filtering, washing and drying.
[0107] In an optional example, the mixing ratio of the lithiated sericite and deionized water is (0.8~1.3) g:100 mL, for example, it can be 0.8g:100mL, 0.85g:100mL, 0.9g:100mL, 0.95g:100mL, 1g:100mL, 1.05g:100mL, 1.1g:100mL, 1.15g:100mL, 1.2g:100mL, 1.25g:100mL or 1.3g:100mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0108] In an optional example, the mass ratio of the lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:(2.5~3.5), for example, it can be 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, 1:3.0, 1:3.1, 1:3.2, 1:3.3, 1:3.4 or 1:3.5, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0109] The present invention specifically limits the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution to 1:(2.5-3.5). With the increase of the amount of hexadecyltrimethylammonium bromide, the interlayer spacing of the mica nanosheets finally obtained shows a trend of first increasing and then decreasing. When the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide is within the numerical range defined by the present invention, a larger interlayer spacing can be obtained and a higher intercalation efficiency can be achieved. When the amount of hexadecyltrimethylammonium bromide is lower than the lower limit of the range defined by the present invention, the interlayer cations of the sericite cannot be completely exchanged by the hexadecyltrimethylammonium bromide chain, resulting in a smaller interlayer spacing of the intercalated sericite, and effective ultrasonic stripping cannot be achieved. When the amount of hexadecyltrimethylammonium bromide used exceeds the upper limit of the range defined in the present invention, too many organic chains tend to accumulate in the interlayer edge region of sericite, blocking the exchange channel between the organic chains and the interlayer cations, resulting in only a small number of hexadecyltrimethylammonium bromide molecular chains being able to successfully enter the interlayers of sericite, replacing lithium ions to achieve organic intercalation modification, while most of the hexadecyltrimethylammonium bromide molecular chains are unable to successfully enter the interlayers of sericite, but are simply adsorbed on the surface of sericite, resulting in low intercalation efficiency.
[0110] In an optional example, the mixing and stirring time of the sericite solution and hexadecyltrimethylammonium bromide is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0111] In an optional example, the temperature for mixing and stirring the sericite solution and hexadecyltrimethylammonium bromide is 70-80°C, for example, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0112] As a preferred technical solution of the present invention, in step (III), the ultrasonic peeling process includes:
[0113] The intercalated sericite is dispersed in ethanol, ultrasonically exfoliated to obtain a sericite dispersion, the sericite dispersion is centrifuged once, the supernatant after the first centrifugation is centrifuged twice, and the precipitate after the second centrifugation is washed and dried to obtain the mica nanosheets.
[0114] In an optional example, the mass ratio of the intercalated sericite to ethanol is 1:(4~5), for example, it can be 1:4.0, 1:4.1, 1:4.2, 1:4.3, 1:4.4, 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9 or 1:5.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0115] In an optional example, the ultrasonic power of the ultrasonic peeling is 400~500W, for example, it can be 400W, 410W, 420W, 430W, 440W, 450W, 460W, 470W, 480W, 490W or 500W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0116] In an optional example, the ultrasonic time of the ultrasonic stripping is 2 to 3 hours, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0117] In an optional example, the rotation speed of the centrifugation is 2000~3000r / min, for example, it can be 2000r / min, 2100r / min, 2200r / min, 2300r / min, 2400r / min, 2500r / min, 2600r / min, 2700r / min, 2800r / min, 2900r / min or 3000r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0118] In an optional example, the centrifugation time is 10 to 20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0119] In an optional example, the rotation speed of the secondary centrifugation is 2000-3000 r / min, for example, it can be 2000 r / min, 2100 r / min, 2200 r / min, 2300 r / min, 2400 r / min, 2500 r / min, 2600 r / min, 2700 r / min, 2800 r / min, 2900 r / min or 3000 r / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0120] In an optional example, the secondary centrifugation time is 10 to 20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0121] As a preferred technical solution of the present invention, in step (III), the process of hydrophobic modification of the surface of the mica nanosheets comprises:
[0122] The mica nanosheets are dispersed in a silane coupling agent solution, mixed and stirred under a water bath heating condition to react, and after the reaction is completed, the modified mica nanosheets are obtained by filtering, washing and drying.
[0123] In an optional example, the silane coupling agent solution is prepared by the following method:
[0124] Anhydrous ethanol and distilled water are uniformly mixed in a volume ratio of (8-9):1 to obtain a mixed solvent, and an acetic acid solution is added dropwise to the mixed solvent to adjust the pH value thereof to 4.5-5.5; a silane coupling agent is added to the mixed solvent, and the mixture is mixed and stirred for 10-20 minutes to hydrolyze the silane coupling agent to obtain a silane coupling agent solution with a mass fraction of 3-5wt%.
[0125] The volume ratio of anhydrous ethanol to distilled water can be 8.0:1, 8.1:1, 8.2:1, 8.3:1, 8.4:1, 8.5:1, 8.6:1, 8.7:1, 8.8:1, 8.9:1 or 9.0:1, the pH value can be 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4 or 5.5, and the mixing time can be 10 min, 11 min, 12 min, 13 min , 14min, 15min, 16min, 17min, 18min, 19min or 20min, the mass fraction of the silane coupling agent solution can be 3.0wt%, 3.2wt%, 3.4wt%, 3.6wt%, 3.8wt%, 4.0wt%, 4.2wt%, 4.4wt%, 4.6wt%, 4.8wt% or 5.0wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0126] In an optional example, the ratio of the mica nanosheets to the silane coupling agent in the silane coupling agent solution is 1g:(0.05~0.06)mL, for example, it can be 1g:0.05mL, 1g:0.051mL, 1g:0.052mL, 1g:0.053mL, 1g:0.054mL, 1g:0.055mL, 1g:0.056mL, 1g:0.057mL, 1g:0.058mL, 1g:0.059mL or 1g:0.06mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0127] The present invention particularly limits the ratio of mica nanosheets to the silane coupling agent in the silane coupling agent solution to 1 g: (0.05-0.06) mL. When the amount of the silane coupling agent exceeds the upper limit of the range defined by the present invention, the hydrophobic modification effect on the mica nanosheets will deteriorate. This is because when the amount of the silane coupling agent is too high, the silane coupling agent itself will undergo a polymerization reaction, resulting in a reduction in the amount of the silane coupling agent coupled and grafted with the mica nanosheets, and the hydrophobicity of the obtained modified mica nanosheets is reduced.
[0128] In an optional example, the mixing and stirring time of the mica nanosheets and the silane coupling agent solution is 30 to 60 minutes, for example, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0129] In an optional example, the temperature for mixing and stirring the mica nanosheets and the silane coupling agent solution is 70-80°C, for example, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0130] As a preferred technical solution of the present invention, in step (IV), the mass fraction of the loaded modified phosphorylated nanocellulose in the composite suspension is 1-2wt%, for example, it can be 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2.0wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0131] In an optional example, the mass ratio of the loaded modified phosphorylated nanocellulose to the modified mica nanosheets is 1:(3~5), for example, it can be 1:3.0, 1:3.2, 1:3.4, 1:3.6, 1:3.8, 1:4.0, 1:4.2, 1:4.4, 1:4.6, 1:4.8 or 1:5.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0132] The present invention particularly limits the mass ratio of the loaded modified phosphorylated nanocellulose to the modified mica nanosheet to be 1: (3-5), the addition of the loaded modified phosphorylated nanocellulose can exert its own mechanical strengthening effect, and at the same time can significantly improve the dispersibility of the modified mica nanosheet in the matrix material, avoid the modified mica nanosheet from agglomerating in the matrix material, thereby causing the stress concentration phenomenon, affecting the mechanical properties of the composite material. However, the amount of the loaded modified phosphorylated nanocellulose should not be too high, when the amount of the loaded modified phosphorylated nanocellulose exceeds the upper limit of the range defined by the present invention, it will cause the viscosity of the matrix material to be too high, which is not conducive to subsequent processing such as painting construction or melt extrusion. At the same time, the amount of the modified mica nanosheet should not be too high, when the amount of the modified mica nanosheet exceeds the upper limit of the range defined by the present invention, agglomeration will still occur, thereby causing the stress concentration phenomenon, affecting the mechanical properties of the composite material.
[0133] In an optional example, the mass fraction of the nonionic surfactant in the composite suspension is 0.5~1.5wt%, for example, it can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0134] In an optional example, the nonionic surfactant includes any one of ethoxylated fatty acid esters, alkanolamides, or fatty alcohol polyoxyethylene ethers, or a combination of at least two thereof.
[0135] In an optional embodiment, the ultrasonic power of the ultrasonic dispersion of the composite suspension is 400-500 W, for example, 400 W, 410 W, 420 W, 430 W, 440 W, 450 W, 460 W, 470 W, 480 W, 490 W or 500 W, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0136] In an optional example, the ultrasonic dispersion time of the composite suspension is 2 to 3 h, for example, 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h or 3.0 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0137] In an optional example, the spray drying process of the composite dispersion is carried out in a spray drying tower.
[0138] In an optional embodiment, the inlet air temperature of the spray drying tower is 150-250°C, for example, it can be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0139] In an optional embodiment, the outlet air temperature of the spray drying tower is 90-100°C, for example, it can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0140] In an optional embodiment, the feed rate of the spray drying tower is 50~100mL / h, for example, it can be 50mL / h, 55mL / h, 60mL / h, 65mL / h, 70mL / h, 75mL / h, 80mL / h, 85mL / h, 90mL / h, 95mL / h or 100mL / h, but is not limited to the listed values. In some optional embodiments, other unlisted values within the numerical range are also applicable.
[0141] Compared to oven drying and freeze drying, the present invention particularly preferably adopts spray drying process, this is because, the abundant hydroxyl functional groups on the surface of nanocellulose give it a high degree of hydrophilicity and gel-like properties, but also cause nanocellulose to form irreversible agglomeration, i.e. "keratinization", during oven drying due to the action of intermolecular hydrogen bonds, thereby losing the nanometer size. The nanocellulose after freeze drying will form a sheet of fiber floccules, and it is also impossible to achieve uniform dispersion of a single nanocellulose. Compared to oven drying and freeze drying, spray drying can obtain fine nanocellulose powder and is simple and time-saving. The particle size after redispersion in the matrix material remains almost unchanged compared to when it was not dried, and the unique advantages of nanocellulose can still be fully utilized.
[0142] In a second aspect, the present invention provides a flame retardant and smoke suppressing nanocellulose-based reinforced modified material prepared by the preparation method described in the first aspect.
[0143] Compared with the prior art, the present invention has the following beneficial effects:
[0144] The present invention compounds the loaded modified phosphorylated nanocellulose and the modified mica nanosheets to prepare a flame retardant and smoke suppressing nanocellulose-based reinforced modified material, which can be used as a performance enhancer for polymers such as coatings, rubbers, plastics, foods, and pharmaceutical materials to improve the product structure and improve the physical and chemical properties of the product, such as mechanical properties, flame retardant properties, and smoke suppression properties. When used, the reinforced modified material provided by the present invention can be added to the base material in a certain proportion, mixed evenly, and then produced according to conventional processes. For example, in the field of coatings, the reinforced modified material provided by the present invention can be added to the coating emulsion in a certain proportion, mixed evenly, and then coated. After drying and forming the film, a paint film coating with excellent mechanical properties, flame retardant properties, and smoke suppression properties can be obtained; in the field of plastics, the reinforced modified material provided by the present invention can be melt-blended and extruded with a polymer material in a certain proportion to obtain a plastic masterbatch with excellent mechanical properties, flame retardant properties, and smoke suppression properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0145] Figure 1 A process flow chart for preparing the nanocellulose-based enhanced modified material provided in Examples 1-5 of the present invention;
[0146] Figure 2 This is a transmission electron microscopy image of the phosphorylated nanocellulose prepared in Example 1 of the present invention;
[0147] Figure 3 This is a transmission electron microscopy image of the modified phosphorylated nanocellulose prepared in Example 1 of the present invention;
[0148] Figure 4 This is a transmission electron microscopy image of the composite modified phosphorylated nanocellulose prepared in Example 1 of the present invention;
[0149] Figure 5 This is a transmission electron microscopy image of the loaded modified phosphorylated nanocellulose prepared in Example 1 of the present invention;
[0150] Figure 6 IR spectra of octadecylamine, phosphorylated nanocellulose prepared in Example 1 of the present invention, and modified phosphorylated nanocellulose;
[0151] Figure 7 This is a scanning electron microscope image of the sericite mica used in Example 1 of the present invention;
[0152] Figure 8 This is a scanning electron microscope image of the activated sericite prepared in Example 1 of the present invention;
[0153] Fig. 9 This is a scanning electron microscope image of the acidified sericite prepared in Example 1 of the present invention;
[0154] Fig.10 This is an infrared spectrum of sericite and mica nanosheets prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0155] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0156] Example 1
[0157] This embodiment provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0158] (1) steam explosion is performed on the cellulose raw material to obtain raw fiber, wherein the steam pressure of the steam explosion is 1 MPa, the steam temperature is 180° C., and the processing time of the steam explosion is 10 min;
[0159] The raw material fiber, diammonium hydrogen phosphate, urea and deionized water are mixed to obtain a suspension, wherein the mass fraction of the raw material fiber in the suspension is 5wt%, the concentration of diammonium hydrogen phosphate is 0.2kg / L, and the concentration of urea is 0.4kg / L; the suspension is crushed at 60°C for 3h to obtain a mixed material; the mixed material is fed into a screw extruder, extruded and dehydrated at a speed of 10rpm to obtain a wet material with a moisture content of 60wt%;
[0160] The wet material is sequentially subjected to heating drying and high-temperature curing to obtain phosphorylated cellulose, wherein the heating drying temperature is 80° C., the heating drying time is 50 minutes, the high-temperature curing temperature is 150° C., and the high-temperature curing time is 30 minutes;
[0161] The phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed solution, wherein the mass fraction of the phosphorylated cellulose in the cellulose mixed solution is 0.5wt%, and the cellulose mixed solution is subjected to mechanical grinding and high-pressure homogenization in sequence, wherein the mechanical grinding is carried out in a colloid mill, the rotation speed of the colloid mill is 2500r / min, the mechanical grinding time is 3h, the high-pressure homogenization pressure is 70MPa, and the high-pressure homogenization time is 90min, and phosphorylated nanocellulose is obtained after high-pressure homogenization;
[0162] Under heating conditions of 40° C., the phosphorylated nanocellulose and the N,N'-carbonyldiimidazole solution are mixed and stirred for 12 hours to react, wherein the N,N'-carbonyldiimidazole solution is composed of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.2 mol / L, and the mass ratio of the phosphorylated nanocellulose to the N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:1, and an intermediate product solution is obtained after the reaction is completed;
[0163] Adding an octadecylamine solution to the intermediate product solution, wherein the octadecylamine solution consists of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.2 mol / L, and the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.1, mixing and stirring at 40° C. for 12 hours to react, filtering, washing and drying after the reaction is completed to obtain modified phosphorylated nanocellulose;
[0164] Dopamine is dissolved in deionized water to obtain a mixed solution with a concentration of 1 g / L, and Tris-HCl buffer is added to the mixed solution to adjust the pH value of the mixed solution to 8.5 to obtain a dopamine solution; modified phosphorylated nanocellulose is dispersed in the dopamine solution, the mass ratio of the modified phosphorylated nanocellulose to dopamine in the dopamine solution is 100:8, mixed and stirred at 40° C. for 24 hours to react, and after the reaction is completed, centrifuged at a speed of 6000 r / min for 30 minutes, the precipitate is washed, and the washed precipitate is freeze-dried at -50° C. for 48 hours to obtain a composite modified phosphorylated nanocellulose;
[0165] (2) Anhydrous ethanol, ammonia solution and deionized water are mixed in a volume ratio of 1:0.03:1.5 to obtain a composite solvent, wherein the mass fraction of the ammonia solution is 25wt%; the composite modified phosphorylated nanocellulose and hexadecyltrimethylammonium bromide obtained in step (1) are added to the composite solvent, wherein the mixing ratio of the composite modified phosphorylated nanocellulose, hexadecyltrimethylammonium bromide and the composite solvent is 0.1g:0.15g:100mL, and the mixture is stirred at 60°C for 2h to obtain a mixed solution; under stirring and heating at 30°C, tetraethyl orthosilicate is added dropwise to the mixed solution, wherein the mass ratio of the composite modified phosphorylated nanocellulose to tetraethyl orthosilicate in the mixed solution is 1:0.1, after all the tetraethyl orthosilicate is added dropwise, stirring is continued at 30°C for 3h, and after the reaction is completed, filtering, washing and freeze-drying are performed, wherein the freeze-drying temperature is -50°C and the freeze-drying time is 48h to obtain the loaded modified phosphorylated nanocellulose;
[0166] (3) calcining the sericite at a high temperature, wherein the heating temperature of the high temperature calcination is 750°C and the holding time is 2 hours, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 8 mol / L, and the ratio of the activated sericite to the nitric acid solution is 2 g:100 mL, and the mixture is mixed and stirred at 80°C for 5 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are mixed uniformly in a mass ratio of 1:8 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 300°C for 6 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;
[0167] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 0.8 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:2.5, mixing and stirring at 70° C. for 3 h, and then filtering, washing and drying to obtain intercalated sericite;
[0168] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:4, ultrasonic peeling was performed at an ultrasonic power of 400 W for 3 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 2000 r / min, the time of the first centrifugation was 20 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 2000 r / min, the time of the second centrifugation was 20 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;
[0169] Anhydrous ethanol and distilled water were uniformly mixed in a volume ratio of 8:1 to obtain a mixed solvent, and an acetic acid solution was added dropwise to the mixed solvent to adjust the pH value thereof to 4.5; silane coupling agent KH550 was added to the mixed solvent, and the mixture was mixed and stirred for 10 minutes to hydrolyze the silane coupling agent KH550 to obtain a silane coupling agent solution with a mass fraction of 3wt%; mica nanosheets were dispersed in the silane coupling agent solution, and the ratio of mica nanosheets to silane coupling agent KH550 in the silane coupling agent solution was 1g:0.05mL, and the mixture was mixed and stirred for 60 minutes under a water bath heating condition of 70°C to react, and after the reaction was completed, the modified mica nanosheets were obtained after filtering, washing and drying;
[0170] (4) The loaded modified phosphorylated nanocellulose obtained in step (2), the modified mica nanosheets obtained in step (3), the ethoxylated fatty acid ester and deionized water are mixed to obtain a composite suspension, wherein the mass fraction of the loaded modified phosphorylated nanocellulose in the composite suspension is 1wt%, the mass ratio of the loaded modified phosphorylated nanocellulose to the modified mica nanosheets is 1:3, the mass fraction of the ethoxylated fatty acid ester in the composite suspension is 0.5wt%, the composite suspension is ultrasonically dispersed at an ultrasonic power of 400W for 3h to obtain a composite dispersion; the composite dispersion is spray-dried in a spray drying tower, the inlet air temperature of the spray drying tower is 150°C, the outlet air temperature is 90°C, and the feeding speed is 50mL / h, and the nanocellulose-based reinforced modified material is obtained after spray drying.
[0171] Figure 2 , Figure 3 , Figure 4 and Figure 5 TEM images of phosphorylated nanocellulose, modified phosphorylated nanocellulose, composite modified phosphorylated nanocellulose and loaded modified phosphorylated nanocellulose prepared in this example, respectively. Figure 2It can be seen that the unmodified phosphorylated nanocellulose presents an intertwined network structure. This is because the unmodified phosphorylated nanocellulose molecular chains contain a large number of hydroxyl functional groups, and it is easy to form a high-energy hydrogen bond network between the molecular chains. Therefore, the phosphorylated nanocellulose molecular chains are very easy to agglomerate, usually existing in the form of a network and unevenly distributed in a certain area. Figure 3 It can be seen that the dispersion uniformity of the modified phosphorylated nanocellulose obtained by CDI-amino grafting modification is improved. Figure 4 It can be seen that a rough structure is formed on the surface of the modified phosphorylated nanocellulose, which is formed by the deposition of polydopamine obtained by oxidative self-polymerization of dopamine on the surface of the modified phosphorylated nanocellulose. Figure 5 It can be seen that nano-silica particles are formed on the surface of the composite modified phosphorylated nanocellulose, and their aspect ratio is significantly reduced.
[0172] Figure 6 The infrared spectra of octadecylamine, phosphorylated nanocellulose and modified phosphorylated nanocellulose prepared in this embodiment are shown in the figure. As can be seen from the figure, in the infrared curves of phosphorylated nanocellulose and modified phosphorylated nanocellulose, at 3417cm -1 、2918cm -1 and 1059~1165cm -1 There are obvious characteristic peaks at 3417cm -1 The stretching vibration peak corresponding to -OH is 2918 cm -1 The stretching vibration peak corresponding to the CH bond is 1059~1165cm -1 The stretching vibration peaks of CO and COC correspond to the modified phosphorylated nanocellulose, which indicates that the modified phosphorylated nanocellulose still retains the carbon skeleton structure of phosphorylated nanocellulose. However, the difference from phosphorylated nanocellulose is that new absorption peaks appear in the infrared curve of modified phosphorylated nanocellulose, such as: 1730cm -1 The stretching vibration peak of -C=O corresponds to the carbamate bond in the molecular chain, 1610 cm -1 and 1469cm -1 The stretching vibration peaks at the positions correspond to the -C=C- and -C=N- in the imidazole ring introduced after CDI activation, which indicates that CDI and octadecylamine have been successfully grafted onto the molecular chain of phosphorylated nanocellulose and a carbamate bond has been formed between CDI and octadecylamine.
[0173] Figure 7 , Figure 8 and Fig. 9 The scanning electron microscope images of the sericite used in this embodiment, the activated sericite prepared in this embodiment and the acidified sericite are shown in FIG. Figure 7, the activated sericite obtained after high temperature activation treatment (such as Figure 8 The surface of the quartz crystal (as shown in Figure 2) has a rough structure, but the crystal structure is not completely destroyed and the lamellae morphology remains intact. Figure 8 , the acidified sericite (such as Fig. 9 The lamella structure of the sericite mica is complete, the surface roughness structure has increased, wrinkles and cracks appear on the surface, and the surface area of the sericite mica lamellae is increased, which is beneficial to the adsorption of lithium ions and cation exchange during the lithiation process.
[0174] Fig.10 The infrared spectra of sericite and mica nanosheets prepared in this example are shown in the figure. It can be seen from the figure that 3622cm -1 and 3448cm -1 The stretching vibration peaks of free water between sericite layers and free -OH on the surface are 1028 cm -1 The peak corresponding to the stretching vibration of Si-O-Si skeleton of sericite is 400~800cm -1 The corresponding Al-O and Si-O bending vibration peaks are found in the infrared spectra of sericite and mica nanosheets, indicating that both contain sericite. The difference is that in the infrared spectra of mica nanosheets, 2918cm -1 and 2851cm -1 The peaks at 1487 cm-1 correspond to the antisymmetric stretching vibration peaks of -CH3 and -CH2- in the molecular chain of hexadecyltrimethylammonium bromide. -1 The peak at 1640 cm corresponds to the bending vibration peak of CN in the molecular chain of hexadecyltrimethylammonium bromide. -1 The corresponding CC absorption vibration peak indicates that the hexadecyl trimethyl ammonium bromide molecular chain has entered the sericite mica layer. In addition, in the infrared spectrum curve of the mica nanosheet modified by organic intercalation, 3622cm -1 The peak intensity at 3448cm -1 The peak intensity at 1028cm is enhanced, which is because the mica nanosheets modified by organic intercalation change from hydrophilic to hydrophobic, and the free water between the layers decreases. -1 The peak intensity at 4° is weakened because the molecular chain of hexadecyltrimethylammonium bromide enters the interlayers of sericite and destroys the skeleton structure to a certain extent.
[0175] Example 2
[0176] This embodiment provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0177] (1) steam explosion is performed on the cellulose raw material to obtain raw fiber, wherein the steam pressure of the steam explosion is 1.2 MPa, the steam temperature is 185° C., and the processing time of the steam explosion is 8 min;
[0178] The raw material fiber, diammonium hydrogen phosphate, urea and deionized water are mixed to obtain a suspension, wherein the mass fraction of the raw material fiber in the suspension is 6wt%, the concentration of diammonium hydrogen phosphate is 0.22kg / L, and the concentration of urea is 0.42kg / L; the suspension is crushed at 65°C for 2.8h to obtain a mixed material; the mixed material is fed into a screw extruder, extruded and dehydrated at a speed of 12rpm to obtain a wet material with a moisture content of 62wt%;
[0179] The wet material is sequentially subjected to heating drying and high-temperature curing to obtain phosphorylated cellulose, wherein the heating drying temperature is 82° C., the heating drying time is 48 minutes, the high-temperature curing temperature is 152° C., and the high-temperature curing time is 28 minutes;
[0180] The phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed solution, wherein the mass fraction of the phosphorylated cellulose in the cellulose mixed solution is 0.8wt%, and the cellulose mixed solution is subjected to mechanical grinding and high-pressure homogenization in sequence, wherein the mechanical grinding is carried out in a colloid mill, the rotation speed of the colloid mill is 2600r / min, the mechanical grinding time is 2.8h, the pressure of the high-pressure homogenization is 80MPa, and the high-pressure homogenization time is 80min, and phosphorylated nanocellulose is obtained after high-pressure homogenization;
[0181] Under heating conditions of 42° C., the phosphorylated nanocellulose and the N,N'-carbonyldiimidazole solution were mixed and stirred for 11.5 hours to react, wherein the N,N'-carbonyldiimidazole solution consisted of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 0.22 mol / L, the mass ratio of the phosphorylated nanocellulose to the N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 1:1.05, and an intermediate product solution was obtained after the reaction was completed;
[0182] Adding an octadecylamine solution to the intermediate product solution, wherein the octadecylamine solution consists of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.22 mol / L, and the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.12, mixing and stirring at 42° C. for 11.5 hours to react, filtering, washing and drying after the reaction is completed to obtain modified phosphorylated nanocellulose;
[0183] Dopamine is dissolved in deionized water to obtain a mixed solution with a concentration of 1.2 g / L, and Tris-HCl buffer is added to the mixed solution to adjust the pH value of the mixed solution to 8.5 to obtain a dopamine solution; modified phosphorylated nanocellulose is dispersed in the dopamine solution, the mass ratio of the modified phosphorylated nanocellulose to dopamine in the dopamine solution is 100:8.5, mixed and stirred at 42° C. for 21 hours to react, and after the reaction is completed, centrifuged at a speed of 6500 r / min for 28 minutes, the precipitate is washed, and the washed precipitate is freeze-dried at -52° C. for 42 hours to obtain a composite modified phosphorylated nanocellulose;
[0184] (2) Anhydrous ethanol, ammonia solution and deionized water are mixed in a volume ratio of 1:0.035:1.8 to obtain a composite solvent, wherein the mass fraction of the ammonia solution is 26wt%; the composite modified phosphorylated nanocellulose and hexadecyltrimethylammonium bromide obtained in step (1) are added to the composite solvent, wherein the mixing ratio of the composite modified phosphorylated nanocellulose, hexadecyltrimethylammonium bromide and the composite solvent is 0.11g:0.16g:100mL, and the mixture is stirred at 62°C for 1.8h to obtain a mixed solution; under stirring and heating at 32°C, tetraethyl orthosilicate is added dropwise to the mixed solution, wherein the mass ratio of the composite modified phosphorylated nanocellulose to tetraethyl orthosilicate in the mixed solution is 1:0.12, and after all the tetraethyl orthosilicate is added dropwise, stirring is continued at 32°C for 2.8h, and after the reaction is completed, filtering, washing and freeze-drying are performed, wherein the freeze-drying temperature is -52°C and the freeze-drying time is 42h to obtain the loaded modified phosphorylated nanocellulose;
[0185] (3) calcining the sericite at a high temperature, wherein the heating temperature of the high temperature calcination is 780°C and the holding time is 1.8 hours, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 9 mol / L, and the ratio of the activated sericite to the nitric acid solution is 2.5 g:100 mL, and the mixture is mixed and stirred at 82°C for 4.8 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are mixed uniformly at a mass ratio of 1:8.5 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 320°C for 5.8 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;
[0186] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 1 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:2.8, mixing and stirring at 72° C. for 2.8 h, and then filtering, washing and drying to obtain intercalated sericite;
[0187] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:4.2, ultrasonic stripping was performed at an ultrasonic power of 420 W for 2.8 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 2200 r / min, the time of the first centrifugation was 18 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 2200 r / min, the time of the second centrifugation was 18 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;
[0188] Anhydrous ethanol and distilled water were uniformly mixed in a volume ratio of 8.2:1 to obtain a mixed solvent, and an acetic acid solution was added dropwise to the mixed solvent to adjust the pH value thereof to 4.8; silane coupling agent KH550 was added to the mixed solvent, and the mixture was mixed and stirred for 12 minutes to hydrolyze the silane coupling agent KH550 to obtain a silane coupling agent solution with a mass fraction of 3.5wt%; mica nanosheets were dispersed in the silane coupling agent solution, and the ratio of mica nanosheets to silane coupling agent KH550 in the silane coupling agent solution was 1g:0.052mL, and the mixture was mixed and stirred for 50 minutes under a water bath heating condition of 72°C to react, and after the reaction was completed, the modified mica nanosheets were obtained after filtering, washing and drying;
[0189] (4) The loaded modified phosphorylated nanocellulose obtained in step (2), the modified mica nanosheets obtained in step (3), the ethoxylated fatty acid ester and deionized water are mixed to obtain a composite suspension, wherein the mass fraction of the loaded modified phosphorylated nanocellulose in the composite suspension is 1.2wt%, the mass ratio of the loaded modified phosphorylated nanocellulose to the modified mica nanosheets is 1:3.5, the mass fraction of the ethoxylated fatty acid ester in the composite suspension is 0.8wt%, and the composite suspension is ultrasonically dispersed at an ultrasonic power of 420 W for 2.8 h to obtain a composite dispersion; the composite dispersion is spray-dried in a spray drying tower, the inlet air temperature of the spray drying tower is 180° C., the outlet air temperature is 92° C., and the feeding rate is 60 mL / h, and the nanocellulose-based reinforced modified material is obtained after spray drying.
[0190] Example 3
[0191] This embodiment provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0192] (1) steam explosion is performed on the cellulose raw material to obtain raw fiber, wherein the steam pressure of the steam explosion is 1.5 MPa, the steam temperature is 190° C., and the processing time of the steam explosion is 7 min;
[0193] The raw material fiber, diammonium phosphate, urea and deionized water are mixed to obtain a suspension, wherein the mass fraction of the raw material fiber in the suspension is 7wt%, the concentration of diammonium phosphate is 0.25kg / L, and the concentration of urea is 0.45kg / L; the suspension is crushed at 70°C for 2.5h to obtain a mixed material; the mixed material is fed into a screw extruder, extruded and dehydrated at a speed of 15rpm to obtain a wet material with a moisture content of 65wt%;
[0194] The wet material is sequentially subjected to heating drying and high-temperature curing to obtain phosphorylated cellulose, wherein the heating drying temperature is 85° C., the heating drying time is 45 minutes, the high-temperature curing temperature is 155° C., and the high-temperature curing time is 25 minutes;
[0195] The phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed solution, wherein the mass fraction of the phosphorylated cellulose in the cellulose mixed solution is 1wt%, and the cellulose mixed solution is subjected to mechanical grinding and high-pressure homogenization in sequence, wherein the mechanical grinding is carried out in a colloid mill, the rotation speed of the colloid mill is 2700r / min, the mechanical grinding time is 2.5h, the pressure of the high-pressure homogenization is 90MPa, and the high-pressure homogenization time is 80min, and phosphorylated nanocellulose is obtained after high-pressure homogenization;
[0196] Under heating conditions of 45° C., the phosphorylated nanocellulose and the N,N'-carbonyldiimidazole solution were mixed and stirred for 11 hours to react, wherein the N,N'-carbonyldiimidazole solution consisted of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 0.25 mol / L, the mass ratio of the phosphorylated nanocellulose to the N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 1:1.1, and an intermediate product solution was obtained after the reaction was completed;
[0197] Adding an octadecylamine solution to the intermediate product solution, wherein the octadecylamine solution consists of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.25 mol / L, and the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.15, mixing and stirring at 45° C. for 11 hours to react, filtering, washing and drying after the reaction is completed to obtain modified phosphorylated nanocellulose;
[0198] Dopamine is dissolved in deionized water to obtain a mixed solution with a concentration of 1.5 g / L, and Tris-HCl buffer is added to the mixed solution to adjust the pH value of the mixed solution to 8.5 to obtain a dopamine solution; modified phosphorylated nanocellulose is dispersed in the dopamine solution, the mass ratio of the modified phosphorylated nanocellulose to dopamine in the dopamine solution is 100:9, mixed and stirred at 45° C. for 18 hours to react, and after the reaction is completed, centrifuged at a speed of 7000 r / min for 25 minutes, the precipitate is washed, and the washed precipitate is freeze-dried at -55° C. for 38 hours to obtain a composite modified phosphorylated nanocellulose;
[0199] (2) Anhydrous ethanol, ammonia solution and deionized water are mixed in a volume ratio of 1:0.04:2 to obtain a composite solvent, wherein the mass fraction of the ammonia solution is 27wt%; the composite modified phosphorylated nanocellulose and hexadecyltrimethylammonium bromide obtained in step (1) are added to the composite solvent, wherein the mixing ratio of the composite modified phosphorylated nanocellulose, hexadecyltrimethylammonium bromide and the composite solvent is 0.12g:0.17g:100mL, and the mixture is stirred at 65°C for 1.5h to obtain a mixed solution; under stirring and heating at 35°C, tetraethyl orthosilicate is added dropwise to the mixed solution, wherein the mass ratio of the composite modified phosphorylated nanocellulose to tetraethyl orthosilicate in the mixed solution is 1:0.15, after all the tetraethyl orthosilicate is added dropwise, stirring is continued at 35°C for 2.5h, and after the reaction is completed, filtering, washing and freeze-drying are performed, wherein the freeze-drying temperature is -55°C and the freeze-drying time is 38h to obtain the loaded modified phosphorylated nanocellulose;
[0200] (3) calcining the sericite at a high temperature, wherein the heating temperature of the high temperature calcination is 800°C and the holding time is 1.5 hours, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 10 mol / L, and the ratio of the activated sericite to the nitric acid solution is 3 g:100 mL, and the mixture is mixed and stirred at 85°C for 4.5 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are mixed uniformly in a mass ratio of 1:9 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 350°C for 5.5 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;
[0201] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 1.1 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:3, mixing and stirring at 75°C for 2.5 hours, and then filtering, washing and drying to obtain intercalated sericite;
[0202] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:4.5, ultrasonic stripping was performed at an ultrasonic power of 450 W for 2.5 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 2500 r / min, the time of the first centrifugation was 15 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 2500 r / min, the time of the second centrifugation was 15 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;
[0203] Anhydrous ethanol and distilled water were uniformly mixed in a volume ratio of 8.5:1 to obtain a mixed solvent, and an acetic acid solution was added dropwise to the mixed solvent to adjust the pH value thereof to 5; silane coupling agent KH550 was added to the mixed solvent, and the mixture was mixed and stirred for 15 minutes to hydrolyze the silane coupling agent KH550 to obtain a silane coupling agent solution with a mass fraction of 4wt%; mica nanosheets were dispersed in the silane coupling agent solution, and the ratio of mica nanosheets to silane coupling agent KH550 in the silane coupling agent solution was 1g:0.055mL, and the mixture was mixed and stirred for 40 minutes under a water bath heating condition of 75°C to react, and after the reaction was completed, the modified mica nanosheets were obtained after filtering, washing and drying;
[0204] (4) The loaded modified phosphorylated nanocellulose obtained in step (2), the modified mica nanosheets obtained in step (3), alkanolamide and deionized water are mixed to obtain a composite suspension, wherein the mass fraction of the loaded modified phosphorylated nanocellulose in the composite suspension is 1.5wt%, the mass ratio of the loaded modified phosphorylated nanocellulose to the modified mica nanosheets is 1:4, the mass fraction of the alkanolamide in the composite suspension is 1wt%, and the composite suspension is ultrasonically dispersed at an ultrasonic power of 450W for 2.5h to obtain a composite dispersion; the composite dispersion is spray-dried in a spray drying tower, the inlet air temperature of the spray drying tower is 200°C, the outlet air temperature is 95°C, and the feeding rate is 70mL / h, and the nanocellulose-based reinforced modified material is obtained after spray drying.
[0205] Example 4
[0206] This embodiment provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0207] (1) steam explosion is performed on the cellulose raw material to obtain raw fiber, wherein the steam pressure of the steam explosion is 1.8 MPa, the steam temperature is 195° C., and the processing time of the steam explosion is 6 min;
[0208] The raw material fiber, disodium hydrogen phosphate, urea and deionized water are mixed to obtain a suspension, wherein the mass fraction of the raw material fiber in the suspension is 8wt%, the concentration of disodium hydrogen phosphate is 0.28kg / L, and the concentration of urea is 0.48kg / L; the suspension is crushed at 75°C for 2.2h to obtain a mixed material; the mixed material is fed into a screw extruder, extruded and dehydrated at a speed of 18rpm to obtain a wet material with a moisture content of 68wt%;
[0209] The wet material is sequentially subjected to heating drying and high-temperature curing to obtain phosphorylated cellulose, wherein the heating drying temperature is 88° C., the heating drying time is 42 minutes, the high-temperature curing temperature is 158° C., and the high-temperature curing time is 22 minutes;
[0210] The phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed solution, wherein the mass fraction of the phosphorylated cellulose in the cellulose mixed solution is 1.2wt%, and the cellulose mixed solution is subjected to mechanical grinding and high-pressure homogenization in sequence, wherein the mechanical grinding is carried out in a colloid mill, the rotation speed of the colloid mill is 2800r / min, the mechanical grinding time is 2.2h, the pressure of the high-pressure homogenization is 90MPa, and the high-pressure homogenization time is 70min, and phosphorylated nanocellulose is obtained after high-pressure homogenization;
[0211] Under heating conditions of 48° C., the phosphorylated nanocellulose and the N,N'-carbonyldiimidazole solution were mixed and stirred for 10.5 hours to react, wherein the N,N'-carbonyldiimidazole solution consisted of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 0.28 mol / L, the mass ratio of the phosphorylated nanocellulose to the N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution was 1:1.15, and an intermediate product solution was obtained after the reaction was completed;
[0212] Adding an octadecylamine solution to the intermediate product solution, wherein the octadecylamine solution consists of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.28 mol / L, and the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.18, mixing and stirring at 48° C. for 10.5 hours to react, filtering, washing and drying after the reaction is completed to obtain modified phosphorylated nanocellulose;
[0213] Dopamine is dissolved in deionized water to obtain a mixed solution with a concentration of 1.8 g / L, and Tris-HCl buffer is added to the mixed solution to adjust the pH value of the mixed solution to 8.5 to obtain a dopamine solution; modified phosphorylated nanocellulose is dispersed in the dopamine solution, the mass ratio of the modified phosphorylated nanocellulose to dopamine in the dopamine solution is 100:9.5, mixed and stirred at 48°C for 15 hours to react, and after the reaction is completed, centrifuged at a speed of 7500 r / min for 23 minutes, the precipitate is washed, and the washed precipitate is freeze-dried at -58°C for 32 hours to obtain a composite modified phosphorylated nanocellulose;
[0214] (2) Anhydrous ethanol, ammonia solution and deionized water are mixed in a volume ratio of 1:0.045:2.2 to obtain a composite solvent, wherein the mass fraction of the ammonia solution is 28wt%; the composite modified phosphorylated nanocellulose and hexadecyltrimethylammonium bromide obtained in step (1) are added to the composite solvent, wherein the mixing ratio of the composite modified phosphorylated nanocellulose, hexadecyltrimethylammonium bromide and the composite solvent is 0.13g:0.18g:100mL, and the mixture is stirred at 68°C for 1.2h to obtain a mixed solution; under stirring and heating at 38°C, tetraethyl orthosilicate is added dropwise to the mixed solution, wherein the mass ratio of the composite modified phosphorylated nanocellulose to tetraethyl orthosilicate in the mixed solution is 1:0.18, after all the tetraethyl orthosilicate is added dropwise, stirring is continued at 38°C for 2.2h, and after the reaction is completed, filtering, washing and freeze-drying are performed, wherein the freeze-drying temperature is -58°C and the freeze-drying time is 32h to obtain the loaded modified phosphorylated nanocellulose;
[0215] (3) calcining the sericite at a high temperature, wherein the heating temperature of the high temperature calcination is 820°C and the holding time is 1.2 h, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 11 mol / L, and the ratio of the activated sericite to the nitric acid solution is 3.5 g:100 mL, and the mixture is mixed and stirred at 88°C for 4.2 h, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are mixed uniformly at a mass ratio of 1:9.5 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 380°C for 5.2 h to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;
[0216] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 1.2 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:3.2, mixing and stirring at 78° C. for 2.2 h, and then filtering, washing and drying to obtain intercalated sericite;
[0217] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:4.8, ultrasonic stripping was performed at an ultrasonic power of 480 W for 2.2 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 2800 r / min, the time of the first centrifugation was 12 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 2800 r / min, the time of the second centrifugation was 12 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;
[0218] Anhydrous ethanol and distilled water were uniformly mixed in a volume ratio of 8.8:1 to obtain a mixed solvent, and an acetic acid solution was added dropwise to the mixed solvent to adjust the pH value thereof to 5.2; silane coupling agent KH560 was added to the mixed solvent, and the mixture was mixed and stirred for 18 minutes to hydrolyze the silane coupling agent KH560 to obtain a silane coupling agent solution with a mass fraction of 4.5wt%; mica nanosheets were dispersed in the silane coupling agent solution, and the ratio of mica nanosheets to silane coupling agent KH560 in the silane coupling agent solution was 1g:0.058mL, and the mixture was mixed and stirred for 40 minutes under a water bath heating condition of 78°C to react, and after the reaction was completed, the modified mica nanosheets were obtained after filtering, washing and drying;
[0219] (4) The loaded modified phosphorylated nanocellulose obtained in step (2), the modified mica nanosheets obtained in step (3), the fatty alcohol polyoxyethylene ether and deionized water are mixed to obtain a composite suspension, wherein the mass fraction of the loaded modified phosphorylated nanocellulose in the composite suspension is 1.8wt%, the mass ratio of the loaded modified phosphorylated nanocellulose to the modified mica nanosheets is 1:4.5, the mass fraction of the fatty alcohol polyoxyethylene ether in the composite suspension is 1.2wt%, the composite suspension is ultrasonically dispersed at an ultrasonic power of 480 W for 2.2 h to obtain a composite dispersion; the composite dispersion is spray-dried in a spray drying tower, the inlet air temperature of the spray drying tower is 220° C., the outlet air temperature is 98° C., and the feeding rate is 80 mL / h, and the nanocellulose-based reinforced modified material is obtained after spray drying.
[0220] Example 5
[0221] This embodiment provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material, such as Figure 1 As shown, the preparation method specifically comprises the following steps:
[0222] (1) steam explosion is performed on the cellulose raw material to obtain raw fiber, wherein the steam pressure of the steam explosion is 2 MPa, the steam temperature is 200° C., and the processing time of the steam explosion is 5 min;
[0223] The raw material fiber, sodium dihydrogen phosphate, urea and deionized water are mixed to obtain a suspension, wherein the mass fraction of the raw material fiber in the suspension is 10wt%, the concentration of sodium dihydrogen phosphate is 0.3kg / L, and the concentration of urea is 0.5kg / L; the suspension is crushed at 80°C for 2h to obtain a mixed material; the mixed material is fed into a screw extruder, extruded and dehydrated at a speed of 20rpm to obtain a wet material with a moisture content of 70wt%;
[0224] The wet material is sequentially subjected to heating and drying and high-temperature curing to obtain phosphorylated cellulose, wherein the heating and drying temperature is 90° C., the heating and drying time is 40 minutes, the high-temperature curing temperature is 160° C., and the high-temperature curing time is 20 minutes;
[0225] The phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed solution, wherein the mass fraction of the phosphorylated cellulose in the cellulose mixed solution is 1.5wt%, and the cellulose mixed solution is subjected to mechanical grinding and high-pressure homogenization in sequence, wherein the mechanical grinding is carried out in a colloid mill, the rotation speed of the colloid mill is 3000r / min, the mechanical grinding time is 2h, the pressure of the high-pressure homogenization is 100MPa, and the high-pressure homogenization time is 60min, and phosphorylated nanocellulose is obtained after high-pressure homogenization;
[0226] Under heating conditions of 50° C., the phosphorylated nanocellulose and the N,N'-carbonyldiimidazole solution are mixed and stirred for 10 hours to react, wherein the N,N'-carbonyldiimidazole solution is composed of N,N'-carbonyldiimidazole and dichloromethane, the concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.3 mol / L, and the mass ratio of the phosphorylated nanocellulose to the N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:1.2, and an intermediate product solution is obtained after the reaction is completed;
[0227] Adding an octadecylamine solution to the intermediate product solution, wherein the octadecylamine solution consists of octadecylamine and dichloromethane, the concentration of octadecylamine in the octadecylamine solution is 0.3 mol / L, and the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:1.2, mixing and stirring at 50° C. for 10 hours to react, filtering, washing and drying after the reaction is completed to obtain modified phosphorylated nanocellulose;
[0228] Dopamine is dissolved in deionized water to obtain a mixed solution with a concentration of 2 g / L, and Tris-HCl buffer is added to the mixed solution to adjust the pH value of the mixed solution to 8.5 to obtain a dopamine solution; modified phosphorylated nanocellulose is dispersed in the dopamine solution, the mass ratio of the modified phosphorylated nanocellulose to the dopamine in the dopamine solution is 100:10, mixed and stirred at 50° C. for 12 hours to react, and after the reaction is completed, centrifuged at a speed of 8000 r / min for 20 minutes, the precipitate is washed, and the washed precipitate is freeze-dried at -60° C. for 24 hours to obtain a composite modified phosphorylated nanocellulose;
[0229] (2) Anhydrous ethanol, ammonia solution and deionized water are mixed in a volume ratio of 1:0.05:2.5 to obtain a composite solvent, wherein the mass fraction of the ammonia solution is 30wt%; the composite modified phosphorylated nanocellulose and hexadecyltrimethylammonium bromide obtained in step (1) are added to the composite solvent, wherein the mixing ratio of the composite modified phosphorylated nanocellulose, hexadecyltrimethylammonium bromide and the composite solvent is 0.15g:0.2g:100mL, and the mixture is stirred at 70°C for 1h to obtain a mixed solution; under stirring and heating at 40°C, tetraethyl orthosilicate is added dropwise to the mixed solution, wherein the mass ratio of the composite modified phosphorylated nanocellulose to tetraethyl orthosilicate in the mixed solution is 1:0.2, after all the tetraethyl orthosilicate is added dropwise, stirring is continued at 40°C for 2h, and after the reaction is completed, filtering, washing and freeze-drying are performed, wherein the freeze-drying temperature is -60°C and the freeze-drying time is 24h to obtain the loaded modified phosphorylated nanocellulose;
[0230] (3) calcining the sericite at a high temperature, wherein the heating temperature of the high temperature calcination is 850°C and the holding time is 1 hour, and activated sericite is obtained after calcination; the activated sericite is dispersed in a nitric acid solution with a concentration of 12 mol / L, and the ratio of the activated sericite to the nitric acid solution is 4 g:100 mL, and the mixture is mixed and stirred at 90°C for 4 hours, and then filtered, washed and dried to obtain acidified sericite; the acidified sericite and lithium nitrate are mixed uniformly at a mass ratio of 1:10 to obtain a mixed powder, and the mixed powder is fed into a muffle furnace, and calcined at 400°C for 5 hours to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain lithiated sericite;
[0231] Dispersing lithiated sericite in deionized water, the mixing ratio of lithiated sericite to deionized water is 1.3 g:100 mL, and mixing evenly to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, the mass ratio of lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:3.5, mixing and stirring at 80° C. for 2 h, and then filtering, washing and drying to obtain intercalated sericite;
[0232] The intercalated sericite was dispersed in ethanol, the mass ratio of the intercalated sericite to ethanol was 1:5, ultrasonic peeling was performed at an ultrasonic power of 500 W for 2 h to obtain a sericite dispersion, the sericite dispersion was centrifuged once, the speed of the first centrifugation was 3000 r / min, the time of the first centrifugation was 10 min, the supernatant after the first centrifugation was centrifuged twice, the speed of the second centrifugation was 3000 r / min, the time of the second centrifugation was 10 min, the precipitate after the second centrifugation was washed and dried to obtain mica nanosheets;
[0233] Anhydrous ethanol and distilled water were uniformly mixed in a volume ratio of 9:1 to obtain a mixed solvent, and an acetic acid solution was added dropwise to the mixed solvent to adjust the pH value thereof to 5.5; a silane coupling agent KH560 was added to the mixed solvent, and the mixture was mixed and stirred for 20 minutes to hydrolyze the silane coupling agent KH560 to obtain a silane coupling agent solution with a mass fraction of 5wt%; mica nanosheets were dispersed in the silane coupling agent solution, and the ratio of the mica nanosheets to the silane coupling agent KH560 in the silane coupling agent solution was 1g:0.06mL, and the mixture was mixed and stirred for 30 minutes under a water bath heating condition of 80°C to react, and after the reaction was completed, the modified mica nanosheets were obtained after filtering, washing and drying;
[0234] (4) The loaded modified phosphorylated nanocellulose obtained in step (2), the modified mica nanosheets obtained in step (3), the fatty alcohol polyoxyethylene ether and deionized water are mixed to obtain a composite suspension, wherein the mass fraction of the loaded modified phosphorylated nanocellulose in the composite suspension is 2wt%, the mass ratio of the loaded modified phosphorylated nanocellulose to the modified mica nanosheets is 1:5, the mass fraction of the fatty alcohol polyoxyethylene ether in the composite suspension is 1.5wt%, the composite suspension is ultrasonically dispersed at an ultrasonic power of 500 W for 2 h to obtain a composite dispersion; the composite dispersion is spray-dried in a spray drying tower, the inlet air temperature of the spray drying tower is 250° C., the outlet air temperature is 100° C., and the feeding rate is 100 mL / h, and the nanocellulose-based reinforced modified material is obtained after spray drying.
[0235] Example 6
[0236] This embodiment provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material. The difference from Embodiment 1 is that in step (1), the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is adjusted to 1:1.1, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0237] Example 7
[0238] This embodiment provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material. The difference from Embodiment 1 is that in step (1), the molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is adjusted to 1:1.5, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0239] Example 8
[0240] This embodiment provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material. The difference from Embodiment 1 is that in step (1), the temperature of the mixed stirring of the intermediate product solution and the octadecylamine solution is adjusted to 30° C., and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0241] Example 9
[0242] This embodiment provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material. The difference from Example 1 is that in step (1), the temperature of the mixed stirring of the intermediate product solution and the octadecylamine solution is adjusted to 60° C., and the other process parameters and operating steps are exactly the same as those in Example 1.
[0243] Example 10
[0244] This embodiment provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material. The difference from Embodiment 1 is that in step (1), the concentration of dopamine in the mixed solution is adjusted to 0.5 g / L, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0245] Embodiment 11
[0246] This embodiment provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material. The difference from Embodiment 1 is that in step (1), the concentration of dopamine in the mixed solution is adjusted to 2.5 g / L, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0247] Example 12
[0248] This embodiment provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material. The difference from Embodiment 1 is that in step (2), the mass ratio of the composite modified phosphorylated nanocellulose to tetraethyl orthosilicate in the mixed solution is adjusted to 1:0.05, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0249] Embodiment 13
[0250] This embodiment provides a method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material. The difference from Embodiment 1 is that in step (2), the mass ratio of the composite modified phosphorylated nanocellulose to tetraethyl orthosilicate in the mixed solution is adjusted to 1:0.25, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.
[0251] Application Examples
[0252] This application example provides a water-based coating, which includes the following components in parts by weight:
[0253] 80 parts of styrene acrylic emulsion;
[0254] 10 parts water;
[0255] 5 parts of ethylene glycol butyl ether;
[0256] 3 parts of nanocellulose-based reinforced modified material;
[0257] BYK-141 defoamer 1 part;
[0258] BYK-346 wetting agent 0.5 parts;
[0259] 0.5 parts of BYK-300 leveling agent.
[0260] Among them, the nanocellulose-based enhanced modified material is the nanocellulose-based enhanced modified material prepared in each embodiment of the present invention.
[0261] According to the formula of the water-based coating provided in this application example, water-based coatings were prepared using the nanocellulose-based reinforced modified materials provided in Examples 1-13, and were named water-based coating 1, water-based coating 2, water-based coating 3, water-based coating 4, water-based coating 5, water-based coating 6, water-based coating 7, water-based coating 8, water-based coating 9, water-based coating 10, water-based coating 11, water-based coating 12 and water-based coating 13 (hereinafter referred to as water-based coatings 1-13).
[0262] Comparative Example
[0263] This comparative example provides a water-based coating, which includes the following components in parts by weight:
[0264] 80 parts of styrene acrylic emulsion;
[0265] 10 parts of deionized water;
[0266] 5 parts of ethylene glycol butyl ether;
[0267] BYK-420 thickener 3 parts;
[0268] BYK-141 defoamer 1 part;
[0269] BYK-346 wetting agent 0.5 parts;
[0270] 0.5 parts of BYK-300 leveling agent.
[0271] The various properties of water-based coatings 1-13 and the water-based coatings provided in the comparative examples were tested. The specific test steps are as follows:
[0272] (1) Pencil hardness test
[0273] The wood was made into a 120×10×2 mm sample strip, and the water-based coatings 1-13 and the water-based coatings provided in the comparative example were evenly coated on the surface, and the sample strips were dried and cured for 7 days. The pencil hardness of the paint film on the surface of the sample strip was tested by the scratch hardness method in accordance with the national standard GB / T6739-2022 "Determination of paint film hardness by pencil method for paints and varnishes".
[0274] (2) Washing resistance test
[0275] The wood was made into a 120×10×2 mm sample strip, and the water-based coatings 1-13 and the water-based coatings provided in the comparative example were evenly coated on the surface, and the sample strips were dried and cured for 7 days. Subsequently, the washability of the paint film was tested in a constant temperature and humidity environment of 23±2°C and 50±5%. The specific steps are as follows:
[0276] Dip the paint film surface of the sample strip in a washing powder solution with a pH value of 9.5-11.0 and a mass fraction of 0.5wt%, fix the sample strip on the scrub resistance tester, scrub the paint film surface repeatedly until the paint film is damaged, and stop the test, and record the number of scrubbing times.
[0277] (3) Limiting oxygen index test
[0278] The wood was made into a 120×10×2mm sample strip, and the water-based coatings 1-13 and the water-based coatings provided in the comparative example were evenly coated on the surface, and the sample strips were dried and cured for 7 days. The sample strips were tested for oxygen index using a JF-3 oxygen index tester in accordance with the national standard GB / T2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test". The limiting oxygen index is the minimum oxygen volume fraction required for continuous combustion of polymer materials in a mixture of nitrogen and oxygen. The specific test steps are as follows:
[0279] Place the sample strip vertically in a mixed atmosphere of oxygen and nitrogen, ignite the sample strip, and adjust the introduction ratio of oxygen and nitrogen so that the sample strip can just burn stably for 3 minutes. Record the oxygen concentration in the mixed atmosphere at this time, which is the limiting oxygen index of the sample strip.
[0280] (4) Cone calorimetry test
[0281] The wood was made into a 120×10×2mm sample strip, and the water-based coatings 1-13 and the water-based coatings provided in the comparative example were evenly coated on the surface. The sample strips were dried and cured for 7 days. The sample strips were subjected to cone calorimetry test using FTT Standard cone calorimeter. The thermal radiation range of the cone calorimeter is 0~100kW / m 2 between.
[0282] The specific test steps are as follows:
[0283] Before the test, the sample strip was weighed and its thickness was measured. The sample strip was wrapped with tin foil in advance and placed in the test area of the cone calorimeter. The paint film on the surface of the sample strip was subjected to thermal radiation treatment. The thermal radiation flux used was 50kW / m 2 After the sample strip is heated, it releases volatile gas and is ignited by an electric spark initiator. A large amount of gas will be generated during the combustion process of the sample strip. A smoke extractor is used to collect the gas generated after the combustion of the sample strip. The gas is analyzed and calculated using a cone calorimeter to obtain the combustion parameters of the sample strip, such as the peak heat release rate, total heat release, peak smoke release rate and total smoke release.
[0284] The test results are shown in Table 1.
[0285] Table 1
[0286] Pencil hardness Limiting oxygen index% <![CDATA[Peak heat release rate kW·m -2 > <![CDATA[Total heat release MJ·m -2 > <![CDATA[Peak smoke release rate m 2 ·s -1 > <![CDATA[Total smoke release amount m 2 ·kg -1 > Example 1 5H 31.3 152.7 75.2 0.035 11.8 Example 2 5H 32.7 150.6 73.8 0.032 10.9 Example 3 5H 33.2 148.5 72.1 0.028 10.3 Example 4 5H 33.8 145.3 70.9 0.024 9.7 Example 5 5H 34.5 147.9 71.6 0.025 9.5 Example 6 2H 26.5 269.5 96.3 0.071 19.3 Example 7 4H 28.4 227.1 87.6 0.053 16.7 Example 8 2H 25.6 286.7 104.2 0.075 19.8 Example 9 4H 29.7 184.6 80.9 0.044 15.1 Example 10 3H 27.2 254.3 92.4 0.065 18.5 Embodiment 11 4H 29.0 208.4 83.1 0.049 15.9 Example 12 H 25.1 301.4 108.7 0.082 20.4 Embodiment 13 3H 27.8 242.8 90.5 0.058 17.2 Comparative Example 2B 24.3 315.3 115.8 0.087 22.5
[0287] It can be seen from the test data provided in Table 1 that the pencil hardness of the paint films of Examples 1-5 is higher than that of Examples 6-13 and the comparative example, which indicates that the nanocellulose reinforcing modifier provided by the present invention can significantly improve the mechanical properties of the paint films. In addition, the limiting oxygen index of the paint films of Examples 1-5 is higher than that of Examples 6-13 and the comparative example. At the same time, the peak heat release rate, total heat release, peak smoke release rate and total smoke release of the paint films of Examples 1-5 are all lower than those of Examples 6-13 and the comparative example, which indicates that the nanocellulose reinforcing modifier provided by the present invention can significantly improve the flame retardant and smoke suppression properties of the paint films.
[0288] It can be seen from the test data of Example 1, Example 6 and Example 7 that the pencil hardness and limiting oxygen index of the paint film of Example 6 and Example 7 are lower than that of Example 1, while the peak heat release rate, total heat release, peak smoke release rate and total smoke release are higher than that of Example 1. This is because the amount of octadecylamine used in Example 6 is too small, and the grafting rate of octadecylamine is too low, which reduces the dispersibility of the loaded modified phosphorylated nanocellulose in the water-based paint, and ultimately affects the mechanical properties, flame retardant properties and smoke suppression properties of the paint film. The amount of octadecylamine used in Example 7 is too large, and the octadecylamine not grafted to the phosphorylated nanocellulose molecular chain will be deposited on the surface of the phosphorylated nanocellulose, making the hydrophobicity of the loaded modified phosphorylated nanocellulose too high, affecting its compatibility with styrene-acrylic emulsion, and causing the loaded modified phosphorylated nanocellulose to settle and stratify in the water-based paint, which ultimately leads to reduced mechanical properties, flame retardant properties and smoke suppression properties of the paint film.
[0289] It can be seen from the test data of Example 1, Example 8 and Example 9 that the pencil hardness and limiting oxygen index of the paint film of Example 8 and Example 9 are lower than that of Example 1, while the peak heat release rate, total heat release, peak smoke release rate and total smoke release are higher than that of Example 1. This is because the reaction temperature in Example 8 is too low, octadecylamine has not been completely melted, and the reaction rate is low, which affects the grafting rate of octadecylamine, causing the dispersibility of the loaded modified phosphorylated nanocellulose in the water-based coating to decrease, and ultimately affecting the mechanical properties, flame retardant properties and smoke suppression properties of the paint film. As a result, the reaction temperature in Example 9 is too high, causing the octadecylamine molecules grafted on the phosphorylated nanocellulose to dissolve and fall off due to the high temperature, which also affects the grafting rate of octadecylamine, and ultimately leads to reduced mechanical properties, flame retardant properties and smoke suppression properties of the paint film.
[0290] It can be seen from the test data of Example 1, Example 10 and Example 11 that the pencil hardness and limiting oxygen index of the paint film of Example 10 and Example 11 are lower than that of Example 1, while the peak heat release rate, total heat release, peak smoke release rate and total smoke release are higher than that of Example 1. This is because the concentration of dopamine in Example 10 is too low, and the polydopamine produced is less, which is not enough to cover all the hydrophobic long chains of octadecylamine on the surface of the modified phosphorylated nanocellulose. During the high-speed dispersion process, the hydrophobic long chains of octadecylamine grafted on the surface of the modified nanocellulose are easy to fall off, which reduces the dispersibility of the loaded modified phosphorylated nanocellulose in the water-based coating, and ultimately affects the mechanical properties, flame retardant properties and smoke suppression properties of the paint film. The concentration of dopamine in Example 11 is too high, exceeding the equilibrium adsorption value, resulting in the desorption of polydopamine adsorbed on the surface of the modified phosphorylated nanocellulose, which also affects the reinforcement effect of octadecylamine, resulting in the reduction of the dispersibility of the loaded modified phosphorylated nanocellulose in the water-based coating, which reduces the mechanical properties, flame retardant properties and smoke suppression properties of the paint film.
[0291] It can be seen from the test data of Example 1, Example 12 and Example 13 that the pencil hardness and limiting oxygen index of the paint film of Example 12 and Example 13 are lower than that of Example 1, while the peak heat release rate, total heat release, peak smoke release rate and total smoke release are higher than that of Example 1. This is because the amount of ethyl orthosilicate used in Example 12 is too small, resulting in too little nano-silicon dioxide generated by hydrolysis, making it difficult to form a continuous and dense carbon layer, thereby affecting the mechanical properties, flame retardant properties and smoke suppression properties of the paint film. The amount of ethyl orthosilicate used in Example 13 is too large, and the excessive nano-silicon dioxide will cause a serious agglomeration effect in the water-based paint, resulting in stress concentration inside the paint film, thereby affecting the mechanical properties of the paint film. At the same time, excessive silicon elements will cause the rigidity of the carbon layer to be too high, which is easy to cause the carbon layer to rupture and cause the combustible gas to overflow, resulting in a decrease in the flame retardant and smoke suppression properties of the paint film.
[0292] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a flame retardant and smoke suppressing nanocellulose-based reinforced modified material, characterized in that: The preparation method comprises: (I) mixing, stirring and heating the phosphorylated nanocellulose and N,N'-carbonyldiimidazole solution to react, and obtaining an intermediate product solution after the reaction is completed; adding an octadecylamine solution to the intermediate product solution, mixing, stirring and heating to react, filtering, washing and drying after the reaction is completed to obtain modified phosphorylated nanocellulose; dispersing the modified phosphorylated nanocellulose in a dopamine solution, mixing, stirring and heating to react, and centrifuging, washing and freeze-drying after the reaction is completed to obtain a composite modified phosphorylated nanocellulose; (II) mixing anhydrous ethanol, an ammonia solution and deionized water to obtain a composite solvent, adding the composite modified phosphorylated nanocellulose and hexadecyltrimethylammonium bromide obtained in step (II) to the composite solvent, mixing, stirring and heating to obtain a mixed solution; under stirring and heating conditions, dripping tetraethyl orthosilicate into the mixed solution, and continuing to stir and heat for a period of time to react after all the tetraethyl orthosilicate has been dripped, filtering, washing and freeze-drying after the reaction is completed to obtain the loaded modified phosphorylated nanocellulose; (III) subjecting sericite to high temperature calcination to obtain activated sericite; subjecting the activated sericite to acidification with a nitric acid solution to obtain acidified sericite; subjecting the acidified sericite to lithiation with lithium nitrate to obtain lithiated sericite; subjecting the lithiated sericite to intercalation modification with hexadecyltrimethylammonium bromide to obtain intercalated sericite; subjecting the intercalated sericite to ultrasonic exfoliation to obtain mica nanosheets; subjecting the mica nanosheets to surface hydrophobic modification with a silane coupling agent to obtain modified mica nanosheets; (IV) Mixing the loaded modified phosphorylated nanocellulose obtained in step (II), the modified mica nanosheets obtained in step (III), a nonionic surfactant and deionized water to obtain a composite suspension, ultrasonically dispersing the composite suspension to obtain a composite dispersion, and spray-drying the composite dispersion to obtain the nanocellulose-based reinforced modified material.
2. The preparation method according to claim 1, characterized in that: In step (I), the phosphorylated nanocellulose is prepared by the following method: The cellulose raw material is subjected to steam explosion to obtain raw fiber, the raw fiber, phosphate, urea and deionized water are mixed to obtain a suspension, the suspension is heated and crushed at the same time to obtain a mixed material; the mixed material is sent to a screw extruder for extrusion dehydration to obtain a wet material; the wet material is sequentially heated and dried and high-temperature cured to obtain phosphorylated cellulose; the phosphorylated cellulose is mixed with deionized water to obtain a cellulose mixed liquid, the cellulose mixed liquid is sequentially subjected to mechanical grinding and high-pressure homogenization to obtain the phosphorylated nanocellulose; The cellulose raw material includes bleached hardwood pulp or bleached softwood pulp; The steam pressure of the steam explosion is 1-2 MPa; The steam temperature of the steam explosion is 180-200°C; The processing time of the steam explosion is 5 to 10 minutes; The mass fraction of the raw material fiber in the suspension is 5-10wt%; The concentration of phosphate in the suspension is 0.2-0.3 kg / L; The phosphate includes any one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, disodium hydrogen phosphate, sodium dihydrogen phosphate, dilithium hydrogen phosphate or lithium dihydrogen phosphate, or a combination of at least two thereof; The concentration of urea in the suspension is 0.4-0.5 kg / L; The heating temperature of the suspension is 60-80°C; The heating time of the suspension is 2 to 3 hours; The screw speed of the screw extruder is 10-20 rpm; The moisture content of the wet material is 60-70wt%; The heating and drying temperature is 80-90°C; The heating and drying time is 40 to 50 minutes; The high temperature curing temperature is 150-160°C; The high temperature curing time is 20 to 30 minutes; The mass fraction of the phosphorylated cellulose in the cellulose mixed solution is 0.5-1.5wt%; The mechanical grinding is carried out in a colloid mill; The rotation speed of the colloid mill is 2500-3000 r / min; The mechanical grinding time is 2 to 3 hours; The pressure of the high pressure homogenization is 70-100 MPa; The high pressure homogenization time is 60 to 90 minutes.
3. The preparation method according to claim 1, characterized in that: In step (I), the N,N'-carbonyldiimidazole solution is composed of N,N'-carbonyldiimidazole and dichloromethane; The concentration of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 0.2-0.3 mol / L; The mass ratio of the phosphorylated nanocellulose to the N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution is 1:(1-1.2); The mixing and stirring time of the phosphorylated nanocellulose and the N,N'-carbonyldiimidazole solution is 10 to 12 hours; The temperature of mixing and stirring the phosphorylated nanocellulose and the N,N'-carbonyldiimidazole solution is 40-50°C; The octadecylamine solution consists of octadecylamine and dichloromethane; The concentration of octadecylamine in the octadecylamine solution is 0.2-0.3 mol / L; The molar ratio of N,N'-carbonyldiimidazole in the N,N'-carbonyldiimidazole solution to octadecylamine in the octadecylamine solution is 1:(1.1-1.2); The mixing and stirring time of the intermediate product solution and the octadecylamine solution is 10 to 12 hours; The temperature of mixing and stirring the intermediate product solution and the octadecylamine solution is 40-50° C.; The dopamine solution is prepared by the following method: Dissolving dopamine in deionized water to obtain a mixed solution with a concentration of 1-2 g / L, adding Tris-HCl buffer to the mixed solution to adjust the pH value of the mixed solution to 8.5, thereby obtaining the dopamine solution; The mass ratio of the modified phosphorylated nanocellulose to the dopamine in the dopamine solution is 100:(8-10); The modified phosphorylated nanocellulose and the dopamine solution are mixed and stirred for 12 to 24 hours; The temperature of mixing and stirring the modified phosphorylated nanocellulose and the dopamine solution is 40-50° C.; The centrifugal speed is 6000-8000 r / min; The centrifugal time is 20 to 30 minutes; The freeze drying temperature is -50 to -60°C; The freeze-drying time is 24 to 48 hours.
4. The preparation method according to claim 1, characterized in that: In step (II), the volume ratio of anhydrous ethanol, ammonia solution and deionized water is 1:(0.03-0.05):(1.5-2.5); The mass fraction of the ammonia solution is 25-30wt%; The mixing ratio of the composite modified phosphorylated nanocellulose, the hexadecyltrimethylammonium bromide and the composite solvent is (0.1-0.15) g: (0.15-0.2) g: 100 mL; The time for mixing and stirring the composite modified phosphorylated nanocellulose, the hexadecyltrimethylammonium bromide and the composite solvent is 1 to 2 hours; The temperature of mixing and stirring the composite modified phosphorylated nanocellulose, the hexadecyltrimethylammonium bromide and the composite solvent is 60-70° C.; Under stirring and heating conditions at 30-40° C., adding tetraethyl orthosilicate dropwise into the mixed solution; The mass ratio of the composite modified phosphorylated nanocellulose to tetraethyl orthosilicate in the mixed solution is 1:(0.1-0.2); After all the ethyl orthosilicate is dropped, continue stirring for 2-3 hours under heating conditions of 30-40°C; The freeze drying temperature is -50 to -60°C; The freeze-drying time is 24 to 48 hours.
5. The preparation method according to claim 1, characterized in that: In step (III), the heating temperature of the high temperature calcination is 750-850°C; The holding time of the high temperature calcination is 1 to 2 hours; The acidification process comprises: dispersing the activated sericite in a nitric acid solution, mixing, stirring and heating, and then filtering, washing and drying to obtain the acidified sericite; The concentration of the nitric acid solution is 8-12 mol / L; The ratio of the activated sericite to the nitric acid solution is (2-4) g:100 mL; The time for mixing and stirring the activated sericite and the nitric acid solution is 4 to 5 hours; The temperature of mixing and stirring the activated sericite and the nitric acid solution is 80-90° C.; The lithiation process comprises: The acidified sericite and lithium nitrate are uniformly mixed to obtain a mixed powder; the mixed powder is sent into a muffle furnace for calcination to obtain a calcined powder, and the calcined powder is filtered, washed and dried to obtain the lithiated sericite; The mass ratio of the acidified sericite to the lithium nitrate is 1:(8-10); The calcination temperature of the mixed powder is 300-400°C; The calcination time of the mixed powder is 5 to 6 hours.
6. The preparation method according to claim 1, characterized in that: In step (III), the intercalation modification process includes: Dispersing the lithiated sericite in deionized water to obtain a sericite solution, adding hexadecyltrimethylammonium bromide to the sericite solution, mixing, stirring and heating, and then filtering, washing and drying to obtain the intercalated sericite; The mixing ratio of the lithiated sericite and deionized water is (0.8-1.3) g:100 mL; The mass ratio of the lithiated sericite to hexadecyltrimethylammonium bromide in the sericite solution is 1:(2.5-3.5); The mixing and stirring time of the sericite solution and hexadecyltrimethylammonium bromide is 2 to 3 hours; The temperature for mixing and stirring the sericite solution and cetyltrimethylammonium bromide is 70-80°C.
7. The preparation method according to claim 1, characterized in that: In step (III), the ultrasonic peeling process includes: The intercalated sericite is dispersed in ethanol, and ultrasonic stripping is performed to obtain a sericite dispersion liquid, the sericite dispersion liquid is centrifuged once, the supernatant after the first centrifugation is taken for a second centrifugation, and the precipitate after the second centrifugation is washed and dried to obtain the mica nanosheets; The mass ratio of the intercalated sericite to ethanol is 1:(4-5); The ultrasonic power of the ultrasonic peeling is 400-500W; The ultrasonic peeling time is 2 to 3 hours; The rotation speed of the primary centrifugation is 2000-3000 r / min; The time of one centrifugation is 10 to 20 minutes; The secondary centrifugation speed is 2000-3000 r / min; The secondary centrifugation time is 10 to 20 minutes.
8. The preparation method according to claim 1, characterized in that: In step (III), the process of hydrophobic modification of the surface of the mica nanosheets comprises: Dispersing the mica nanosheets in a silane coupling agent solution, mixing and stirring under a water bath heating condition to react, and filtering, washing and drying after the reaction to obtain the modified mica nanosheets; The silane coupling agent solution is prepared by the following method: Anhydrous ethanol and distilled water are uniformly mixed in a volume ratio of (8-9):1 to obtain a mixed solvent, and an acetic acid solution is added dropwise to the mixed solvent to adjust the pH value thereof to 4.5-5.5; a silane coupling agent is added to the mixed solvent, and the mixture is stirred for 10-20 minutes to hydrolyze the silane coupling agent to obtain a silane coupling agent solution with a mass fraction of 3-5 wt %; The ratio of the mica nanosheets to the silane coupling agent in the silane coupling agent solution is 1 g: (0.05-0.06) mL; The mixing time of the mica nanosheets and the silane coupling agent solution is 30 to 60 minutes; The temperature for mixing and stirring the mica nanosheets and the silane coupling agent solution is 70-80°C.
9. The preparation method according to claim 1, characterized in that: In step (IV), the mass fraction of the loaded modified phosphorylated nanocellulose in the composite suspension is 1-2 wt %; The mass ratio of the loaded modified phosphorylated nanocellulose to the modified mica nanosheets is 1:(3-5); The mass fraction of the nonionic surfactant in the composite suspension is 0.5-1.5wt%; The nonionic surfactant includes any one or a combination of at least two of ethoxylated fatty acid esters, alkanolamides or fatty alcohol polyoxyethylene ethers; The ultrasonic power of the ultrasonic dispersion of the composite suspension is 400-500W; The ultrasonic dispersion time of the composite suspension is 2 to 3 hours; The spray drying process of the composite dispersion is carried out in a spray drying tower; The air inlet temperature of the spray drying tower is 150-250°C; The outlet air temperature of the spray drying tower is 90-100°C; The feeding speed of the spray drying tower is 50-100 mL / h.
10. A flame retardant and smoke suppressing nanocellulose-based reinforced modified material prepared by the preparation method according to any one of claims 1 to 9.